Spherical Nanostructures
By developing spherical nanostructures of 20-50nm size, using their strong multivalent metal ion affinity, radioactive isotopes are effectively sent to tumor tissue, solving the problems of excessive size, poor stability and insufficient binding of existing nanocarriers, and achieving efficient cancer imaging and treatment.
Patent Information
- Application Number
- JP2024550179
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-08
- Filing Date
- 2023-03-08
- Publication Date
- 2025-04-30
AI Technical Summary
In cancer treatment, existing nanocarriers have problems such as excessive size, poor stability and insufficient binding to radioisotopes, making it difficult to effectively send radioisotopes to tumor tissue.
A spherical nanostructure with an average flow mechanical diameter of 20-50nm was developed. The nanostructure consists of a central part, an anchor layer and a cladding. The central part contains a bisphosphate acid group. The anchor layer and the cladding are connected by silicon oxygen bonds to form a nanocarrier with high affinity to multivalent metal ions.
The effective accumulation of nanocarriers in tumor tissues and the stable combination of radioisotopes has been achieved, and the effect of cancer imaging and treatment has been improved.
Smart Images

Figure 2025513684000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to bioinert chelating polymer nanostructures that have applications in whole body radiation therapy and cancer imaging. [Background technology]
[0002] The gold standard of cancer treatment is surgery. When surgery alone is not curative, multimodality treatment plans including chemotherapy and radiation therapy are used. Although the intensity, location, and timing of external radiation can be well controlled and adjusted, drawbacks associated with this technique include destruction of normal tissue in the path of the beam, as well as damage to tissue surrounding the tumor. The risk of damaging surrounding healthy tissues makes external radiation therapy inconvenient for tumors located deep inside and tumors located adjacent to vital organs. Moreover, high radiation doses are often required to penetrate the tissue. Moreover, external radiation therapy often requires patients to visit the hospital daily for an extended period of time to be effective.
[0003] Total body radiation therapy, in which radioactive material is delivered internally to the tumor, offers a solution to many of the above-mentioned disadvantages associated with external radiation therapy.
[0004] Currently, the most commonly used radionuclides for total body radiation therapy in the clinic are beta emitters. Beta emitters with energies between 0.1 and 2.2 MeV are ideal for the treatment of small to large clusters of tumor cells. Beta particles of such energies can therefore target tumor cells in close proximity to neovasculature due to their maximal tissue penetration range (1-10 mm) and their ability to indirectly kill cells along longer path lengths due to the cross-fire effect. 131 Radionuclides such as I are used alone, as in the treatment of thyroid cancer, or are conjugated to monoclonal antibodies or peptides to allow for tumor-targeted radioimmunotherapy. 90Ibritumomab tiuexan (Zevalin®) with Y and 131 Tositumomab (Bexxar®) conjugated with I are two examples of approved radioimmunotherapy regimens that target B lymphocytes to treat B-cell non-Hodgkin's lymphoma.
[0005] The clinical use of alpha emitters is less common, but 223 Some, such as Ra (Xofigo®), have shown clinical potential.
[0006] The use of radionuclides in systemic radiotherapy in most cases requires the use of a carrier, as the radionuclides do not have favorable pharmaceutical properties as the atom or simple salt.
[0007] Recent advances in nanotechnology have led to the development of novel nanocarriers designed for cancer detection and screening, in vivo molecular and cellular imaging, and therapeutic drug delivery. However, despite the large number of publications on nanosized carriers for cancer therapeutics, relatively few have made it into clinical trials and only a handful have been approved by the FDA.
[0008] Some approaches involve biodegradable materials that allow for the rapid or slow release of loaded therapeutic agents.
[0009] WO 2004 / 040972 discloses microspheres comprising a polymer hydrogel with radioactive particles, the microspheres being larger than 100 nm.
[0010] European Patent Application Publication No. 2923712(A1) (WO 2015 / 144891) discloses spherical nanostructures having a hydrodynamic diameter (Dh) of 8-100 nm, including a central portion and a peripheral portion, which may contain a radionuclide chelated thereto and may be used for imaging and / or radiotherapy. Summary of the Invention
[0011] Many of the known approaches to radioisotope therapy, including purported nanocarriers, suffer from the drawback that they are not actually nanocarriers because they are larger than 100 nm, and also suffer from the drawback that they do not effectively deliver the radioisotope to tumor tissue due to their large size. Furthermore, many of the known nanocarriers are only stable for a short period of time and / or do not bind the radionuclide strongly enough. The purpose of the present disclosure is to solve these problems. [Means for solving the problem]
[0012] According to a first aspect, the above and other objects are achieved in whole or at least in part by a plurality of spherical nanostructures as defined in claim 1. According to this claim, the above object is achieved by a plurality of spherical nanostructures having an average hydrodynamic diameter of 20 to 50 nm, each nanostructure having: A central moiety comprising a monomer residue according to formula (I), TIFF2025513684000002.tif56170 formula, - Each R 1 , R 2 , R 3 , R 4 , R 5 , and R 6 is independently selected from the group consisting of H, a negative charge, and a covalent bond; - Each R 7 , R 8 , R 9 , and R 10 is independently selected from the group consisting of H, a negative charge, and lower alkyl; R 7 , R 8 , R9 , and R 10 At least 95% of all of the groups are H or negatively charged; - n is an integer from 2 to 5; m is an integer from 2 to 5; The central part and an anchor layer surrounding the central portion, the anchor layer comprising a monomer residue according to formula (II): TIFF2025513684000003.tif29170 formula, - Each R 11 , R 12 , R 13 , R 14 , R 15 , and R 16 is independently selected from the group consisting of H, a negative charge, and a covalent bond; - p is 1 or 2; An anchor layer; a coating layer surrounding the anchor layer, the coating layer comprising a monomer residue according to formula (III): TIFF2025513684000004.tif56170 formula, - Each R 17 , R 18 , R 19 , R 20 , R 21 , and R 22 is independently selected from the group consisting of H, a negative charge, and a covalent bond; - q is an integer from 2 to 5; - r is an integer from 2 to 5; - Each R 23 and R 24 is independently selected from the group consisting of H and lower alkyl; - s is an integer from 30 to 105; - t is an integer from 30 to 105; A coating layer; The polymer nanostructure comprises:
[0013] The covalent bond is a covalent bond to the remainder of the nanostructure.
[0014] Such nanostructures are strong chelators of multivalent metal ions and are highly biocompatible.
[0015] The core (also referred to as the core nanostructure or central portion) comprises a chelating bisphosphonate group capable of chelating a polyvalent metal ion.
[0016] The anchor layer bonds the core to the coating layer.
[0017] The coating layer protects the nanostructures from agglomeration and makes them highly biocompatible.
[0018] The nanostructure of the present disclosure has a hydrodynamic diameter of 20 to 50 nm. Nanostructures with such a particle size are suitable for tumor targeting by the EPR effect (enhancing vascular permeability and retention effect).
[0019] Preferably, the nanostructures have a hydrodynamic diameter of 21-40 nm. It is advantageous to use nanostructures with a hydrodynamic diameter of 22-37 nm, since this results in a strong accumulation of the nanostructures in the tumor tissue. Thus, the hydrodynamic diameter of the nanostructures may preferably be 23-35 nm, such as 25-30 nm.
[0020] Typically, the dispersity of the nanostructures is low, such as less than 1.6, such as between 1 and 1.6, or between 1 and 1.4, or between 1.1 and 1.3, or between 1.13 and 1.27, as measured by DLS.
[0021] Preferably, the dispersity is less than 1.4, such as less than 1.3, such as less than 1.2.
[0022] Preferably, n and m are independently 2 or 3. Even more preferably, n and m are both 3.
[0023] In some cases, p is 1.
[0024] In other cases, p is 2.
[0025] Preferably, p is 1.
[0026] Preferably, q and r are both 3.
[0027] In some cases, s and t are both between 35 and 80, or both between 45 and 65, or both between 55 and 60.
[0028] Preferably, s and t each are in the range of 35-55, or in the range of 45-65, or in the range of 60-80.
[0029] Preferably, R 23 and R 24 are each methyl or ethyl.
[0030] Preferably, q and r are both 3, s and t are both 35 to 55, and R 23 and R 24 are all methyl.
[0031] According to one embodiment, X represents the ratio of the number of monomer residues in the central portion to the total number of monomer residues in the nanostructure. CP is 5% to 58%, and indicates the ratio of the number of monomer residues in the anchor layer to the total number of monomer residues in the nanostructure, X AL is 39% to 93%, and indicates the ratio of the number of monomer residues in the coating layer to the total number of monomer residues in the nanostructure, X CL is 0.75% to 4.5%, and 70% < (X CP +X AL +X CL )≦100%.
[0032] According to one embodiment, monomer residues according to formula (I) constitute at least 70% of the monomer residues of the core portion, and / or monomer residues according to formula (II) constitute at least 70% of the monomer residues of the anchor layer, and / or monomer residues according to formula (III) constitute at least 70% of the monomer residues of the coating layer.
[0033] According to another embodiment, the average hydrodynamic diameter is 22 to 37 nm, n=3, m=3, p=1, q=3, r=3, and R 23 and R 24 is independently selected from the group consisting of lower alkyl, and / or X represents the ratio of the number of monomer residues in the core portion to the total number of monomer residues in the nanostructure. CP is 20% to 40%, and indicates the ratio of the number of monomer residues in the anchor layer to the total number of monomer residues in the nanostructure, X AL is 60% to 85%, and indicates the ratio of the number of monomer residues in the coating layer to the total number of monomer residues in the nanostructure, X CL is 1.5% to 4%, and 81.5% < (X CP +X AL +X CL )≦100%.
[0034] Preferably, the lower alkyl is methyl and / or ethyl.
[0035] Thus, the average hydrodynamic diameter may be 22-37 nm, n=3, m=3, p=1, q=3, r=3, and R 23 and R 24 is independently selected from the group consisting of lower alkyl.
[0036] Specifically, the average hydrodynamic diameter is 22 to 37 nm, n = 3, m = 3, p = 1, q = 3, r = 3, and R 23 and R 24 is independently selected from the group consisting of methyl and ethyl.
[0037] Preferably, X represents the ratio of the number of monomer residues in the central portion to the total number of monomer residues in the nanostructure. CP is 20% to 40%, and indicates the ratio of the number of monomer residues in the anchor layer to the total number of monomer residues in the nanostructure, X AL is 60% to 85%, and indicates the ratio of the number of monomer residues in the coating layer to the total number of monomer residues in the nanostructure, X CL is 1.5% to 4%, and 81.5% < (X CP +X AL +X CL )≦100%. Preferably, the lower alkyl is methyl and / or ethyl.
[0038] Preferably, the average hydrodynamic diameter is 22 to 37 nm, n=3, m=3, p=1, q=3, r=3, and R 23 and R 24 is independently selected from the group consisting of lower alkyl, and X represents the ratio of the number of monomer residues in the core portion to the total number of monomer residues in the nanostructure. CP is 20% to 40%, and indicates the ratio of the number of monomer residues in the anchor layer to the total number of monomer residues in the nanostructure, X AL is 60% to 85%, and indicates the ratio of the number of monomer residues in the coating layer to the total number of monomer residues in the nanostructure, X CL is 1.5% to 4%, and 81.5% < (X CP +X AL +X CL )≦100%. Preferably, the lower alkyl is methyl and / or ethyl.
[0039] According to a further embodiment, R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 R 17 , R 18 , R19 , R 20 , R 21 , and R 22 At least 50% of all of the groups are covalent bonds, which are covalent bonds to the remainder of the polymer structure.
[0040] According to yet another embodiment, the spherical nanostructures further comprise one or more radionuclides. Such nanostructures can be used in the treatment and / or imaging of cancer.
[0041] The radionuclide may be a radionuclide suitable for imaging, such as PET imaging or SPECT imaging.
[0042] The radionuclide for PET imaging is gallium-68( 68 Ga).
[0043] The radionuclide for SPECT imaging is technetium-99m in the form of the trivalent cation ( 99m Tc 3+ ).
[0044] The radionuclide may be a radionuclide suitable for radiotherapy and / or imaging.
[0045] The radionuclide for imaging and / or radiotherapy is lutetium-177( 177 Lu).
[0046] The radionuclide for imaging and / or radiotherapy is yttrium-90 ( 90 Y).
[0047] The multiple nanostructures may carry an average of 0.5 to 2 radioisotopes per nanostructure.
[0048] According to a further embodiment, the radionuclide is 177 This is Lu.
[0049] According to a second aspect, there is provided a plurality of spherical nanostructures according to the present disclosure for use as a medicament.
[0050] Notably, nanostructures containing radionuclides, nanostructures containing non-radioactive isotopes, and even empty nanostructures, i.e., nanostructures without chelated polyvalent metal ions, can be used as pharmaceuticals.
[0051] According to a third aspect, there is provided a plurality of spherical nanostructures according to the present disclosure comprising a radionuclide for use in the treatment and / or imaging of cancer.
[0052] According to a fourth aspect, there is provided the use of a plurality of spherical nanostructures according to the present disclosure as carriers of radionuclides. In such cases, the nanocarriers are "empty" as described above.
[0053] According to a fifth aspect, there is provided a pharmaceutical composition comprising a plurality of spherical nanostructures according to the present disclosure, water, and at least one excipient.
[0054] The at least one excipient can be a stabilizer, an antioxidant, a cryoprotectant, a preservative, and / or an antibiotic.
[0055] A pharmaceutical composition may contain two or more excipients.
[0056] The pharmaceutical composition may include an antioxidant.
[0057] The antioxidant is preferably thioglycerol and / or gentisic acid. Nanostructures formulated with thioglycerol and / or gentisic acid do not pose the risk of producing calcium oxalate precipitates when administered to a patient together with calcium.
[0058] The pharmaceutical composition may include thioglycerol and gentisic acid.
[0059] In some cases, the pharmaceutical composition includes an antioxidant other than a sulfite or ascorbate.
[0060] In some cases, the antioxidant is not sodium metabisulfite. Sodium metabisulfite inhibits degradation of the nanostructures due to oxidation of the polyethylene glycol chains in the coating layer. Surprisingly, it has been found that sodium metabisulfite is a less suitable excipient for the formulation of nanostructures according to the present disclosure because sodium metabisulfite interferes with the binding of metal ions to the nanostructures.
[0061] The pharmaceutical composition may include a cryoprotectant, which is preferably glycerol.
[0062] The pharmaceutical composition may include antioxidants and cryoprotectants.
[0063] The pharmaceutical composition may contain two antioxidants and one cryoprotectant.
[0064] The pharmaceutical composition may include thioglycerol, gentisic acid, and glycerol.
[0065] According to one embodiment, the pharmaceutical composition further comprises 0.1-10 mg / ml thioglycerol, 0.03-3 mg / ml gentisic acid, and 3-300 mg / ml glycerol.
[0066] According to a sixth aspect, there is provided a pharmaceutical composition according to the present disclosure for use as a medicament.
[0067] According to a seventh aspect, there is provided a pharmaceutical composition according to the present disclosure for use in the treatment and / or imaging of cancer, the pharmaceutical composition comprising a plurality of spherical nanostructures according to the present disclosure comprising a radionuclide.
[0068] According to an eighth aspect, there is provided a method of radiolabeling a plurality of spherical nanostructures with a multivalent cationic radionuclide, the method comprising: a) providing a solution having a pH of less than 3.5 and comprising a plurality of spherical nanostructures, preferably the nanostructures being "empty" nanostructures in accordance with the present disclosure (i.e., containing no radionuclides or polyvalent metal ions); b) contacting the solution of step a) with a pharma- ceutical acceptable salt of a radionuclide; and c) adjusting the pH of the solution to greater than 6; Includes.
[0069] Notably, the same process steps can be used to load nanostructures with non-radioactive polyvalent metal ions.
[0070] Preferably, the solution in step a) is an aqueous solution.
[0071] The solution of step a) may further comprise one or more excipients, such as stabilizers, antioxidants, cryoprotectants, preservatives, and / or antibiotics.
[0072] In step a), the solution preferably has a pH of less than 3.
[0073] The pharma- ceutically acceptable salt of the radionuclide used in step b) is typically used as a solution of the radioisotope. Contacting the solution of nanostructures with the radioisotope can be achieved by mixing the solution of nanostructures with a solution of the radioisotope.
[0074] The radionuclide in step b) may be used in an amount of 0.01 to 2 atoms per nanostructure, such as 0.5 to 1 atom of the radionuclide per nanostructure.
[0075] After step b) and before carrying out step c), it is advantageous to incubate the solution for some time. Preferably, this incubation is carried out at a slightly elevated temperature, such as 40° C. to 80° C., such as 50° C. to 70° C., such as 50° C. to 60° C. The incubation time is preferably at least 15 minutes, such as 30 minutes to 3 hours.
[0076] Thus, step b) may further comprise contacting the solution of step a) with a pharma- ceutically acceptable salt of the radionuclide and then incubating the solution at a temperature between 40°C and 80°C for at least 15 minutes.
[0077] The adjustment of the pH in step c) can be achieved by adding a buffer solution to the solution of nanostructures. It is also envisaged to adjust the pH by the addition of a strong base such as an alkali hydroxide or an alkaline earth metal hydroxide.
[0078] In step c), the pH may be adjusted by mixing the solution of step b) with an aqueous buffer solution having a pH above 6.
[0079] After step c), it is advantageous to incubate the solution for some time before use of the radiolabeled nanostructures. Preferably, this incubation is carried out at a slightly elevated temperature, such as 40° C. to 80° C., such as 50° C. to 70° C., such as 50° C. to 60° C. The incubation time is preferably at least 15 minutes, such as 30 minutes to 3 hours.
[0080] The adjustment of the pH in step c) may be performed by the addition of a buffer containing Tris at a pH above 7.5.
[0081] This solution may be incubated between steps b) and c) at 50° C. to 70° C. for 30 minutes to 2 hours.
[0082] This solution may be incubated at 50° C.-70° C. for 1-3 hours after step c) before the radiolabeled nanostructures are used.
[0083] In one embodiment, in step a), the solution has a pH of less than 3, and / or step b) further comprises incubating the solution of step a) after contacting it with a pharma- ceutically acceptable salt of the radionuclide at a temperature between 40°C and 80°C for at least 15 minutes, and / or in step c), the pH is adjusted by mixing the solution of step b) with an aqueous buffer solution having a pH greater than 6.
[0084] The radionuclide in step b) is gallium-68 ( 68 Ga), technetium-99m in the form of trivalent cation ( 99m Tc 3+ ), Lutetium-177( 177 Lu), Yttrium-90 ( 90 Y), and samarium-153 ( 153 Sm).
[0085] According to a ninth aspect, a kit is provided comprising an aqueous solution of "empty" spherical nanostructures (i.e., containing no radionuclides or polyvalent metal ions) according to the present disclosure, at a pH below 3.5, in an aqueous solution of a pharma- ceutically acceptable buffer having a pH of at least 6, and instructions for use enabling the implementation of a method of radiolabeling according to the present disclosure.
[0086] Optionally, the kit further comprises a mixing container, an apparatus for sterile filtration, a pharma- ceutically acceptable diluent, a centrifugal filter, and equipment for shielding from ionizing radiation.
[0087] The kits may be used in radiopharmacy to prepare single or small doses of radiolabeled nanostructures for use in imaging and / or treatment of pathological conditions such as cancer.
[0088] The kits can be used in combination with a radioisotope source to generate radiolabeled nanostructures suitable for intravenous use.
[0089] The kit may further comprise a mixing vessel suitable for use in steps b) and c) of the above method. The vessel may be of a suitable size to contain the solution of radiolabeled nanostructures obtained at the end of the radiolabeling process, or may be much larger so as to allow dilution of the solution of radiolabeled nanostructures to a much larger volume. Such dilution may be advantageous when the radiolabeled nanostructures are to be administered by slow infusion.
[0090] The kit may further include equipment for sterile filtration, such as a syringe filter, a syringe, and a receiving vessel.
[0091] The kit may further comprise a pharma- ceutically acceptable diluent, such as saline (0.90% w / v NaCl in water) or a calcium-containing buffer.
[0092] The kit may further include a quality control device, which may damage the centrifugal filter and allow quantification of radioisotope binding by determining the radioactivity of the permeate. Such a quality control device may also include components necessary to perform the chromatographic method, such as TLC plates (thin layer chromatography plates) suitable for controlling the type and radiochemical purity of the radiolabeled nanostructures, eluents, and sample preparation components for analysis by HPLC.
[0093] The kit may further include equipment for shielding against ionizing radiation. Such equipment may include a shielded container suitable for storing and transporting containers for radioactive materials. Such a shielded container may be of a size and shape suitable for enclosing the containers that are part of the kit. Such equipment for shielding against ionizing radiation may also include shielded equipment for handling liquids, such as shielded syringes.
[0094] The kit may also include secondary and tertiary containers that allow the components of the kit to be assembled into one or a few units suitable for commercial storage and shipping of the kit. Such containers may include paper and / or plastic boxes and / or plastic or paper bags. Such containers may be suitable for freezer storage of the kit or portions of the kit.
[0095] The kit may also include one or more identifiers, such as a bar code or an RFID (radio frequency identification) chip. Such identifiers may be present in or on the kit, or in one or more containers or containers contained in the kit. The identifiers may be used to uniquely identify the kit for quality control or inventory purposes.
[0096] The present disclosure also relates to the use of nanostructures according to the present disclosure as intermediates in the manufacture of pharmaceutical compositions.
[0097] Other objects, features, and advantages of the present disclosure will become apparent from the following detailed description, from the experimental data, and from the appended claims. It is noted that the present disclosure relates to all possible combinations of features.
[0098] In general, all terms used in the claims should be interpreted according to their ordinary meaning in the art, unless expressly stated otherwise herein. Any reference to "a / an / the [component, means, step, etc.]" should be interpreted in an open-ended manner as referring to at least one example of said component, means, step, etc., unless expressly stated otherwise. The steps of any method disclosed herein do not have to be performed in the exact order disclosed, unless expressly stated otherwise.
[0099] As used herein, the term "compromising" and variations of the term are not intended to exclude other additives, ingredients, excipients, integers, or steps.
[0100] Definition of Terms As used herein, the term "nanostructure" refers to entities whose overall particle size is in the nano range, i.e., 100 nm or less. As used herein, the term excludes structures that typically have an inorganic core and an organic coating, often referred to as "core-shell nanoparticles" or simply "nanoparticles."
[0101] As used herein, the term "spherical" is intended to describe a shape whose minor axis is equal to or greater than half of its major axis, i.e., the length of the longest axis passing through the center (centre of gravity) of the structure is equal to or less than twice the length of the shortest axis passing through the same point. For a non-limiting illustration of this definition, see Figure 1.
[0102] As used herein, the term "spherical nanostructures" refers to nanostructures as discussed above that have an essentially spherical morphology or shape, which is meant to exclude shapes such as flakes, rods, tubes, toroids, chains, and ribbons.
[0103] As used herein, the term "hydrodynamic diameter" refers to the diameter of a hypothetical hard sphere diffusing at the same rate as the particles in solution, i.e., the diameter of an equivalent hard sphere calculated from the diffusion coefficient according to the Stokes-Einstein equation. This term is also known as the "Stokes diameter" or "Stokes-Einstein diameter". Hydration and shape are included in the behavior of the sphere. The diffusion coefficient is then calculated from time-dependent light scattering data obtained, for example, by dynamic light scattering (DLS). Other technical methods for measuring the diffusion coefficient of nanostructures are known to those skilled in the art and may be used instead. In such cases, the measurements should be referenced against DLS measurements. As a comparison, bovine serum albumin has been measured to have a hydrodynamic diameter of 6.5 nm by DLS in saline (150 mM NaCl) at room temperature at pH 7. Depending on whether number average, volume average, or scattering intensity average is used, the calculated values may vary slightly. The volume average is generally the most useful since it indicates how the bulk of the material is sized. Mean diameter (or mean hydrodynamic diameter) referred to herein means the volume-average value when measured in saline or 8% (vol / vol) aqueous ethylene glycol at pH 7 and room temperature.
[0104] As used herein, the term "DLS" is an acronym for Dynamic Light Scattering, a particle size measurement technique, which may also be referred to as Photon Correlation Spectroscopy or Quasi-Elastic Light Scattering. DLS diameters given herein and in the claims, unless otherwise specified, refer to the average of the volume-weighted peaks of a sample measured at 25°C in an aqueous solution of ionic strength equivalent to 150 mM NaCl, also referred to as saline, or in up to 8% (volume / volume) aqueous ethylene glycol. In other words, the hydrodynamic diameters specified herein refer to the average of the volume-weighted peaks of a sample measured by DLS at 25°C in an aqueous solution of ionic strength equivalent to 150 mM NaCl, also referred to as saline, or in 8% ethylene glycol (volume / volume) in saline.
[0105] As used herein, the term "dispersity" is a measure of the width of the particle size distribution of a sample of polymers or nanostructures. The term "dispersity" is used in situations where the term polydispersity was previously used. For most applications, it is preferable to have as narrow a particle size distribution around the mean value as possible, i.e., a low dispersity. For a sample with perfectly uniform particle size, the dispersity is 1, for a non-uniform sample, the dispersity is greater than 1. Dispersity can be calculated in different ways, M w / M n or equivalently, M v / M n As a ratio of M w is the weight average molecular weight, M n is the number average molecular weight, M v is the volume average molecular weight. In this specification, the inventors follow the recommendation by the International Union of Pure and Applied Chemistry (Pure Appl. Chem., Vol. 81, No. 2, pp. 351-353, 2009. doi:10.1351 / PAC-REC-08-05-02) to determine the degree of dispersion of the nanostructure sample. Similarly, TIFF2025513684000005.tif6170 Define it as TIFF2025513684000006.tif6170, d v is the volume mean diameter as measured by DLS, and d n is the number average diameter as measured by DLS. Another way to express the dispersity of a material is to compare it to a known particle size standard. As a non-limiting example illustrated here, a suitable particle size standard could be bovine serum albumin (BSA), or thyroglobulin, or empty cowpea mosaic virus (CPMV) VLPs.
[0106] As used herein, the term "molecular weight" refers to the molecular weight of a compound having a specific molecular structure, or the weight-average molecular weight, also called mass-average molar mass or weight-average molar mass, of a compound that contains a polymeric portion, and the number of monomers of the polymeric portion varies between different individual molecules.Thus, the molecular weight of a compound having a specific molecular structure is the molecular weight calculated based on the number and nature of atoms of the compound, or the molecular weight measured, for example, by mass spectrometry.The molecular weight of a compound that contains a polymeric portion refers to the weight-average molecular weight, also called mass-average molar mass or weight-average molar mass, which can be determined, for example, by gel filtration chromatography or size exclusion chromatography (SEC). More specifically, the weight average molecular weight may be determined according to ISO 16014-1:2019 and ISO 16014-5:2019 ("Determination of average molecular weight and molecular weight distribution of polymers using size-exclusion chromatography"), or according to ISO 16014-1:2019 in combination with any of ISO 16014-2:2019 through ISO 16014-4:2019. Alternatively, the weight average molecular weight may be determined by SEC and confirmed using liquid chromatography-mass spectrometry (LC-MS) or high performance liquid chromatography (HPLC).
[0107] As used herein, SEC-ELSD is an acronym for Size Exclusion Chromatography with Evaporative Light Scattering Detection.
[0108] As used herein, HPLC-ELSD is an acronym for High Performance Liquid Chromatography with Evaporative Light Scattering Detection.
[0109] As used herein, the term "ICP-OES" is an acronym for Inductively Coupled Plasma - Optical Emission Spectrometry. ICP-OES is a technique used to determine the elemental composition in a sample.
[0110] A "monomer" is a molecule that can be covalently linked to other molecules of the same type, and optionally, other types of molecules, to form polymers, ie, macromolecules composed of multiple monomer residues.
[0111] The term "monomer residue" refers to the atoms from one monomer unit that has been incorporated into a larger polymer. Depending on how the monomers are linked, all of the atoms in the monomer may be retained in the monomer residue, or some may be lost during bond formation.
[0112] As used herein, the term "polymeric group" refers to the polymeric portion of a chemical structure, i.e., the polymeric group comprises multiple monomeric residues. The monomeric residues may be the same or different. The polymeric group may be linear or branched. The termini of the polymeric group may comprise a different structure than the remainder of the polymeric group. In many cases, it will be clear to one of skill in the art how the polymeric group will be attached to the remainder of the chemical structure of which it forms a part.
[0113] By "crosslinking" we mean the connection between two different chains in a polymer. It is usually formed by the reaction of a multifunctional monomer (i.e., a crosslinker) that is added during the formation of the polymer. Crosslinks can also be introduced, for example, by radiation treatment, chemical means, or heat. For the nanostructures of the present disclosure, which are network polymers of monomers with multiple branching capabilities, the usual expression of crosslinking degree becomes somewhat inappropriate. For simplicity, we describe only the average number of bonds between monomers. For example, if a monomer can form six bonds with other molecules, and on average three of them are filled, we avoid the term crosslinking degree and describe that there are "on average three bonds with other monomers," or sometimes "on average three bonds out of six possible with other monomers."
[0114] The term "crosslinked" refers to the structure formed after at least one crosslink has been formed.
[0115] As used herein, the term "polymer backbone" refers to a group of covalently linked atoms that form a network structure with multiple crosslinks. Such a polymer backbone is formed by linking suitable monomers and / or oligomers (i.e., molecular complexes consisting of several monomer residues) via covalent bonds.
[0116] The term "degree of polymerization" is usually expressed as the chain length or by the molecular weight of the polymer. The degree of polymerization can be measured by mass spectrometry, gel filtration, or dynamic light scattering.
[0117] When the degree of polymerization is given as a range herein, it is understood by those skilled in the art to mean that the majority, such as the majority, such as more than 80%, or such as more than 90%, or such as more than 95%, of the polyethylene glycol groups have a degree of polymerization that falls within the given range. It is also understood that a small percentage of the polymer groups present may have a degree of polymerization outside the given range, and this may include both higher and lower degrees of polymerization than the given range. When the degree of polymerization is given as a single value, it is understood that the value means the average or typical degree of polymerization, unless otherwise specified.
[0118] Herein, multiple ethylene glycol units linked together are referred to as polyethylene glycol, a polyethylene glycol chain (PEG chain).
[0119] The term "chelating group" refers to a chemical group that can compete well with water for electrostatic binding of a positively charged ion. A single chelating group does not bind very strongly, but when multiple chelating groups surround a positively charged ion, a synergistic binding enhancement occurs. This is called chelation.
[0120] As used herein, the terms "covalently attached" and "covalently bound" are synonymous and have the meaning known to those of skill in the art.
[0121] As used herein, the term "independently selected" means that each of the different components mentioned preceding the term is selected from the group that follows the term independently or separately from the selection of the other mentioned components.
[0122] The term "geminal bisphosphonate group" refers to two phosphonate groups separated by one carbon atom, i.e., the phosphonate groups are attached to the same carbon atom. Compounds containing such geminal bisphosphonate groups are often referred to as 1,1-bisphosphonates (or 1,1-diphosphonates). The phosphonate group in the geminal bisphosphonate group may be substituted.
[0123] The term "radionuclide" means an unstable form of a chemical element that undergoes radioactive decay resulting in the emission of alpha, beta, and / or gamma rays.
[0124] As used herein, the expression "radionuclide for imaging and / or radiotherapy" refers to actinium-225 ( 225 Ac), copper-62( 62 Cu), Copper-64( 64 Cu), Copper-67( 67 Cu), Gallium-67( 67 Ga), Gallium-68( 68 Ga), Holmium-166( 166 Ho), Indium-111( 111 In), Pb-212( 212 Pb), Lutetium-177( 177 Lu), Radium-223 ( 223 Ra), Rhenium-186( 186 Re), rhenium-188( 188 Re), Rubidium-82 ( 82 Rb), Samarium-153( 153 Sm), Strontium-89 ( 89 Sr), Technetium-99m ( 99m Tc 3+ ), Thallium-201( 201 Tl), thorium-227( 227 Th), Yttrium-86( 86 Y), Yttrium-90 ( 90 Y), and zirconium-89 ( 89The expression "radionuclide for imaging and / or radiotherapy" also encompasses combinations of two or more of the abovementioned radionuclides.
[0125] As used herein, the expression "radionuclide for imaging" refers to copper-62 ( 62 Cu), Copper-67( 67 Cu), Gallium-67( 67 Ga), Gallium-68( 68 Ga), Indium-111 ( 111 In), Lutetium-177( 177 Lu), Rhenium-186( 186 Re), Rubidium-82 ( 82 Rb), Technetium-99m ( 99m Tc 3+ ), Thallium-201( 201 Tl), Yttrium-86( 86 Y), and zirconium-89 ( 89 The expression "radionuclide for imaging" also encompasses combinations of two or more of the abovementioned radionuclides.
[0126] As used herein, the expression "radionuclide for PET imaging" refers to copper-62 ( 62 Cu), Gallium-68( 68 Ga), Rubidium-82( 82 Rb), Yttrium-86( 86 Y), and zirconium-89 ( 89 The expression "radionuclide for PET imaging" also encompasses combinations of two or more of the abovementioned radionuclides.
[0127] As used herein, the expression "radionuclide for SPECT imaging" refers to gallium-67 ( 67 Ga), Indium-111 ( 111 In), Technetium-99m ( 99m Tc 3+ ), Lutetium-177( 177 Lu), and Thallium-201 ( 201Tl). The expression "radionuclide for SPECT imaging" also encompasses combinations of two or more of the abovementioned radionuclides.
[0128] As used herein, the expression "radionuclide for radiotherapy" refers to actinium-225 ( 225 Ac), Copper-64( 64 Cu), Copper-67( 67 Cu), Holmium-166( 166 Ho), lead-212( 212 Pb), Lutetium-177( 177 Lu), Radium-223 ( 223 Ra), Rhenium-186( 186 Re), rhenium-188( 188 Re), Samarium-153( 153 Sm), Strontium-89 ( 89 Sr), Thorium-227( 227 Th), and Yttrium-90 ( 90 The expression "radionuclide for radiotherapy" also encompasses combinations of two or more of the abovementioned radionuclides.
[0129] As used herein, the expression "radionuclide for PET imaging and radiotherapy" refers to actinium-225 ( 225 Ac), copper-62( 62 Cu), Copper-64( 64 Cu), Copper-67( 67 Cu), Gallium-68( 68 Ga), Holmium-166( 166 Ho), lead-212( 212 Pb), Lutetium-177( 177 Lu), Radium-223 ( 223 Ra), Rhenium-186( 186 Re), rhenium-188( 188 Re), Rubidium-82 ( 82 Rb), Samarium-153( 153 Sm), Strontium-89 ( 89 Sr), Thorium-227( 227 Th), Yttrium-90(90 Y), and zirconium-89 ( 89 The expression "radionuclide for PET imaging and radiotherapy" also encompasses combinations of two or more of the abovementioned radionuclides.
[0130] As used herein, the expression "radionuclide for SPECT imaging and radiotherapy" refers to actinium-225 ( 225 Ac), Copper-64( 64 Cu), Copper-67( 67 Cu), Gallium-67( 67 Ga), Holmium-166( 166 Ho), Indium-111( 111 In), Pb-212( 212 Pb), Lutetium-177( 177 Lu), Radium-223 ( 223 Ra), Rhenium-186( 186 Re), rhenium-188( 188 Re), Samarium-153( 153 Sm), Strontium-89 ( 89 Sr), Technetium-99m ( 99m Tc 3+ ), Thallium-201( 201 Tl), thorium-227( 227 Th), and Yttrium-90 ( 90 The expression "radionuclide for SPECT imaging and radiotherapy" also encompasses a combination of two or more of the abovementioned radionuclides.
[0131] As used herein, the term "bioinert" refers to a material that is biocompatible, i.e., non-harmful to mammals and mammalian cells, and at the same time, stable to degradation in the human body for a period of one week or more (less than 10% degradation).
[0132] As used herein, the term "oxysilane" refers to any organic compound in which one or more oxygen atoms are bonded to a silicon atom. Non-limiting examples include: The file is TIFF2025513684000007.tif34170.
[0133] As used herein, the term "organosilane" means an organic compound that contains one or more carbon-silicon bonds.
[0134] As used herein, the term "alkoxysilane" means any compound that contains one or more carbon-oxygen-silicon moieties.
[0135] As used herein, the terms "siloxane bond," "siloxane linkage," and "siloxane network" refer to moieties that contain Si-O-Si.
[0136] As used herein, the terms "hydrocarbon" and "hydrocarbon chain" are used to denote an organic residue composed of hydrogen and carbon. A hydrocarbon may be fully saturated or may contain one or more unsaturations. A hydrocarbon according to the present disclosure may contain any number of carbon atoms from 1 to 50.
[0137] As used herein, the term "alkyl" refers to a straight or branched chain, fully saturated (no double or triple bonds) hydrocarbon group. As used herein, an alkyl group can have 1 to 15 carbon atoms. Typical alkyl groups include, but are in no way limited to, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tertiary butyl, pentyl, hexyl, and the like.
[0138] As used herein, the term "lower alkyl" means an alkyl having 1 to 8 carbon atoms.
[0139] As used herein, the term "lower alcohol" means an alcohol having from 1 to 8 carbon atoms.
[0140] Numeric ranges: whenever used herein, unless otherwise specified, a numerical range such as "1 to 8" or "1-8" refers to each integer within the given range, for example, "1 to 8 carbon atoms" and "1-8 carbon atoms" means that an alkyl group may consist of 1 carbon atom, 2 carbon atoms, 3 carbon atoms, etc., up to 8 carbon atoms. However, there are some exceptions that will be apparent to those skilled in the art. In particular, whenever a range is given herein for a molar ratio, such as the Si / P molar ratio, diameter or particle size, pH, duration, concentration, osmolality, or temperature of a nanostructure, the range includes all decimals within the range, including the upper and lower limits.
[0141] As used herein, the term "alkoxy" refers to the formula -OR, where R is lower alkyl, such as methoxy, ethoxy, n-propoxy, 1-methylethoxy (isopropoxy), n-butoxy, iso-butoxy, sec-butoxy, tert-butoxy, amyloxy, iso-amyloxy, etc. Alkoxy groups in accordance with the present disclosure may be optionally substituted.
[0142] As used herein, the term "priming" refers to a material that is applied to another material, object, surface, substrate, interface, or structure to aid, improve, promote, enable, stabilize, or enhance the adhesion of, connection with, spreading of, wetting by, reaction with, bonding to, surface coverage by, or integration with a third material. Primer can be used as a verb meaning to apply a primer (material) (to something) or as the name of the process of applying a primer. It is generally clear to one skilled in the art which form of the term "priming" is used. A material, object, surface, substrate, interface, or structure that has been primed is said to be primed.
[0143] Thus, the term "primed nanostructure" is used to describe a core nanostructure surrounded by an anchor layer as described below.
[0144] The term "coated nanostructures" (or nanostructures having a coating) is used to describe materials that can be produced from the nanostructures of the present disclosure by the addition of one or more layers of additional material. Often, such coated nanostructures are intended for use in radioisotope therapy.
[0145] As used herein, the term "coating" refers to a layer of material applied to a surface to impart one or more properties to the surface. Often, the coating is covalently attached to the surface. Often, the surface is a nanostructured surface. Often, the properties imparted to the surface include inertness, such as bioinertness. The term "coating" can also refer to the process of applying a coating to a surface, and the term "coat" can be used as a verb meaning "to apply a coating to." It will generally be clear to one of ordinary skill in the art which form of the term "coating" is to be used in a particular case.
[0146] As used herein, the term "resin" is defined as an insoluble organic material.
[0147] As used herein, the term "v / v" stands for volume / volume.
[0148] As used herein, 90.0% (vol / vol) aqueous ethylene glycol means a mixture of 90.0% (vol / vol) ethylene glycol and 10.0% (vol / vol) water.
[0149] As used herein, the term "w / w" stands for weight / weight.
[0150] As used herein, the term "w / v" stands for weight / volume.
[0151] As used herein, the term "Tris" means tris(hydroxymethyl)aminomethane.
[0152] By way of example, embodiments of the present teachings will now be described with reference to the accompanying drawings, in which: [Brief description of the drawings]
[0153] [Figure 1] FIG. 1 is an explanatory diagram of a spherical shape. [Diagram 2] FIG. 2 is a structural diagram of a nanostructure showing a partial structure of the nanostructure. [Diagram 3] FIG. 3 shows the 1H-NMR spectra of the core nanostructure (top chart) and the primed nanostructure (bottom chart). [Figure 4] FIG. 4 shows the 31P-NMR spectrum of the core nanostructure. [Diagram 5] FIG. 5 shows the 1H-NMR spectrum of the coated nanostructures. [Figure 6] FIG. 6 is a diagram of the chemical structure of a section of a nanostructure. [Figure 7] FIG. 7 shows tumor growth curves for treated and untreated tumor-bearing mice. [Figure 8] FIG. 8 shows a process scheme illustrating the steps for fabricating nanostructures. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0154] The present disclosure relates to spherical polymeric nanostructures suitable for use as carriers of radioisotopes (also called radionuclides) for imaging and cancer therapy.
[0155] The rationale for the suitability of nanosized materials as tumor-targeting radiation carriers is related to the enhanced vascular permeability and retention (EPR) effect. The EPR effect is based on the fact that capillaries in healthy tissues are practically impermeable to molecules larger than 3-4 nm, while capillaries in rapidly growing tumor tissues are much leakier. In addition, solid tumors tend to lack functional lymphatic vessels. These features combine to limit the removal of extravasated nanomaterials from most solid tumors. EPR-mediated drug targeting is commonly referred to as passive tumor targeting, since it relies exclusively on the pathological properties of the target tissue, i.e., increased leakiness and poor lymphatic drainage.
[0156] Although by no means definitive or limiting, the EPR effect is believed to be in many cases the basis for the advantageous tumor delivery properties of nanostructures according to the present disclosure.
[0157] Notably, nanostructures according to the present disclosure are above the threshold at which they would be excreted through the kidneys causing damage and / or being lost from the body, while at the same time being small enough (<100 nm in diameter) to leak through imperfect capillaries, diffuse through the extracellular matrix, and deliver radioactivity to tumor cells. Nanostructures according to the present disclosure have particle size and surface properties suitable for tumor targeting via the EPR effect.
[0158] The nanostructures are bioinert because, if they were biodegradable, for example, radioisotopes, if present, would be lost from the nanostructures in an undesirable and uncontrolled manner, thereby causing radiation damage to vital organs.
[0159] Nanostructures The nanostructures have hydrodynamic diameters of 20-50 nm, are strong chelators of polyvalent metal ions, and are highly biocompatible.
[0160] Nanostructures are strong chelators of multivalent cations, and therefore they are less suitable as carriers of neutral or anionic radionuclides.
[0161] The nanostructures are polymeric and comprise a highly crosslinked siloxane network.
[0162] The nanostructure comprises three substructures: a chelating core, an anchor layer, and a coating. The core (also referred to as the core nanostructure or central portion) comprises a chelating bisphosphonate group. The anchor layer connects the core to the coating layer. The coating layer protects the nanostructure from aggregation and makes the nanostructure highly biocompatible. The coating layer comprises polyethylene glycol that is bonded to the anchor layer via a siloxane bond.
[0163] The present disclosure relates to a plurality of spherical nanostructures having an average hydrodynamic diameter of 20 to 50 nm, each nanostructure comprising: A central moiety comprising a monomer residue according to formula (I), TIFF2025513684000008.tif55170 formula, - Each R 1 , R 2 , R 3 , R 4 , R 5 , and R 6 is independently selected from the group consisting of H, a negative charge, and a covalent bond; - Each R 7 , R 8 , R 9 , and R 10 is independently selected from the group consisting of H, a negative charge, and lower alkyl; R 7 , R 8 , R 9 , and R 10 At least 95% of all of the groups are H or negatively charged; - n is an integer from 2 to 5; m is an integer from 2 to 5; The central part and an anchor layer surrounding the central portion, the anchor layer comprising a monomer residue according to formula (II): TIFF2025513684000009.tif30170 formula, - Each R 11 , R 12 , R 13 , R 14 , R 15 , and R 16 is independently selected from the group consisting of H, a negative charge, and a covalent bond; - p is 1 or 2; An anchor layer; a coating layer surrounding the anchor layer, the coating layer comprising a monomer residue according to formula (III): TIFF2025513684000010.tif52170 formula, - Each R 17 , R 18 , R 19 , R 20 , R 21 , and R 22 is independently selected from the group consisting of H, a negative charge, and a covalent bond; - q is an integer from 2 to 5; - r is an integer from 2 to 5; - Each R 23 and R 24 is independently selected from the group consisting of H and lower alkyl; - s is an integer from 30 to 105; - t is an integer from 30 to 105; A coating layer; The polymer nanostructure comprises:
[0164] The various parts of the nanostructure are described in detail below.
[0165] Nanostructures are usually fabricated and / or used as a plurality of nanostructures, typically, but not limited to, as a solution. A composition comprising nanostructures of the present disclosure always comprises a plurality of nanostructures. Nanostructures can be characterized by a statistical measure, such as, but not limited to, average diameter, average molecular weight, dispersity, density, concentration, or a particle size measure, such as the percentage passing through a particular calibrated filter having a nominal cutoff value for molecular weight.
[0166] The nanostructures of the present disclosure have a hydrodynamic diameter of 20 to 50 nm, which makes them suitable for tumor targeting via the EPR effect.
[0167] Preferably, the nanostructures have a hydrodynamic diameter of 21 to 40 nm.
[0168] It is advantageous to use nanostructures with a hydrodynamic diameter of 22-37 nm, as this results in strong accumulation of the nanostructures in the tumor tissue (see Example 12).
[0169] Thus, the hydrodynamic diameter of the nanostructures may preferably be from 23 to 35 nm, such as from 25 to 30 nm.
[0170] Nanostructures exist as multiple nanostructures with slightly different sizes and structures. When a single size (diameter) of multiple nanostructures is given, it should be understood as some measure of the center of the size distribution, most often the average size (mean diameter). When a size is given as a range, it should be understood that the said measure of the center of the size distribution falls within the range, and that a portion of the size distribution of multiple nanostructures may be larger or smaller than the range. The width of the size distribution of nanostructures can be expressed by the dispersity.
[0171] In many applications, it is desirable to have a particle size distribution as narrow as possible. The nanostructures of the present disclosure have the advantage of having a fairly narrow particle size distribution. Typically, the dispersity is low, such as less than 1.6, such as 1-1.6, or 1-1.4, or 1.1-1.3, or 1.13-1.27, as measured by DLS and according to the definition given above.
[0172] Thus, in one embodiment, the dispersity is less than 1.4.
[0173] In another embodiment, the dispersity of the nanostructures is less than 1.3.
[0174] In a further embodiment, the dispersity of the nanostructures is less than 1.2.
[0175] The nanostructures of the present disclosure are polymeric and include a crosslinked polymer network. The polymer network includes monomer residues that can form up to six bonds with other monomer residues. Most of the monomer residues in the polymer network include two silicon atoms, and each silicon atom can form three siloxane bonds with other silicon atoms.
[0176] The polymer network contains siloxane bonds between monomer residues.
[0177] The polymer networks of the nanostructures are highly branched and densely cross-linked to form dense three-dimensional networks.
[0178] Each monomer residue of the nanostructure according to the present disclosure can form bonds with up to six adjacent monomer residues. It is clear to those skilled in the art that it is essentially impossible to achieve complete cross-linking, i.e., each monomer residue is bonded to six adjacent monomer residues. Instead, some monomer residues have some silanol groups that do not form bonds with other silicon atoms.
[0179] The average number of bonds per monomer residue to other monomer residues has been found to be a useful measure of the degree of crosslinking in nanostructures. Typically, nanostructures of the present disclosure have more than three bonds per monomer residue to other monomer residues.
[0180] Since the formation of a siloxane bond from two silanols is formally a condensation reaction releasing one water molecule, the average number of bonds per monomer residue to other monomer residues can be estimated from the elemental composition of the nanostructure: 2Si-OH → Si-O-Si + H2O.
[0181] Example 7 provides an example of such a determination of the average number of bonds per monomer residue to other monomer residues from the elemental composition of a nanostructure, showing in this example that the average number of bonds per monomer residue to other monomer residues is greater than 4, which corresponds to 68% of the theoretical maximum number of bonds per monomer residue of 6.
[0182] It has been discovered that the synthesis conditions which result in highly crosslinked nanostructures also result in nanostructures which are good chelators of metal ions.
[0183] As described above, the nanostructure comprises three substructures. The polymer network of each substructure comprises monomer residues of different structures. The central portion or core comprises monomer residues bearing chelating groups. The central portion is surrounded by an anchor layer. The anchor layer is surrounded by a coating layer. The coating layer comprises polyethylene glycol. The various substructures are described in more detail below.
[0184] FIG. 2C shows a schematic diagram of the nanostructure structure.
[0185] The thickness of the anchor layer is half the difference in hydrodynamic diameter between the core nanostructure and the primed nanostructure (i.e., the core nanostructure surrounded by the anchor layer), i.e., (D) in FIG. 2B. B -D A) / 2, and is preferably 0.6 to 5 nm.
[0186] The thickness of the coating layer is half the difference in hydrodynamic diameter between the primed and coated nanostructures, i.e., (D) in Figure 2C. C -D B ) / 2, and is preferably 1 to 15 nm.
[0187] In Figure 6, a schematic diagram of the molecular structure of a portion of a nanostructure according to the present disclosure is shown. The shaded portion represents the anchor layer, the area above the shaded portion represents the coating layer, and the area below the shaded portion represents the central portion of the nanostructure (core nanostructure). The chemical and substructures of the nanostructure in Figure 6 are not necessarily drawn to scale.
[0188] The central portion enables the nanostructure to bind strongly to the radionuclide.
[0189] The anchor layer strongly bonds the coating to the nanostructures.
[0190] The coating layer protects the nanostructures from aggregation, makes them highly water soluble, and also makes them highly biocompatible, allowing them to circulate for a long time in the body.
[0191] The monomer residues of the core (i.e., central portion), the anchor layer, and the coating layer are bonded to each other and to the monomer residues of the other substructures via siloxane bonds, Si-O-Si.
[0192] At the interface between substructures of a nanostructure, monomer residues of one substructure are bonded to monomer residues of another substructure via siloxane bonds, and the interface between the substructures may involve a gradual intermixing of monomer residues of the two substructures rather than an abrupt change from one type of monomer residue to another.
[0193] Measuring the individual sizes of substructures is often difficult, and it is often useful to use the size of the nanostructure intermediate used to synthesize the nanostructure as an approximation of the size of the substructures derived from that intermediate.
[0194] It is less useful to express particle size in terms of degree of polymerization and / or molecular weight, rather than hydrodynamic diameter. However, this is another way to conceptualize the structure. The degree of polymerization is included as a guide, rather than as a limitation. For example, for a nanostructure with a core diameter of 17.5 nm derived from 7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane by hydrolytic condensation polymerization, the estimated nanostructure core density is 1.649 g / ml, the estimated degree of polymerization of the central portion is about 7,700 monomers, and the molecular weight calculated from the volume and density measured by DLS is about 2.7 MDa.
[0195] The relative amounts of different monomer residues present in a nanostructure can be expressed as a mole fraction, i.e., the number of monomer residues of a particular type in the nanostructure or plurality of nanostructures divided by the total number of monomer residues in the nanostructure or plurality of nanostructures.
[0196] The mole fractions of the various monomer residues can be analyzed by a number of methods known in the art.
[0197] One method for estimating the mole fraction of monomer residues is the combination of hydrolytic depolymerization and mass spectrometry (MS). According to this method, a sample of nanostructures is digested in an alkaline medium, which results in hydrolysis of the siloxane bonds of the polymer network, resulting in a solution of hydrolyzed monomer residues and / or oligomers of hydrolyzed monomer residues. The hydrolyzed monomer residues and / or oligomers of hydrolyzed monomer residues are identified, for example, by LC-MS analysis, and a calibrated relative amount is obtained by comparison with a hydrolyzed solution of the monomer.
[0198] Alternatively, monomer residues may be identified by a combination of hydrolytic depolymerization and mass spectrometry, and relative amounts determined by elemental analysis.
[0199] Nanostructures according to the present disclosure may be synthesized by a bottom-up process, as shown in Figure 8. In such a bottom-up process, a central portion is first formed, Figure 2, 2A, in the absence of monomers forming an anchor layer or a coating layer, to form a core nanostructure. An anchor layer is applied to the core nanostructure, in the absence of monomers of a coating layer, to form a primed nanostructure, Figure 2, 2B. A coating layer is applied to the primed nanostructure, to form a coated nanostructure, Figure 2, 2C.
[0200] The formation of the central portion, anchor layer, and coating layer can be achieved by hydrolysis condensation polymerization of precursors containing -Si(OR) groups, where R is a lower alkyl. In particular, precursors bearing triethoxysilyl groups are suitable for the synthesis of nanostructures according to the present disclosure.
[0201] Nanostructures according to the present disclosure are preferably synthesized with core nanostructures having hydrodynamic diameters between 13 and 35 nm. The synthesis of nanostructures is described in more detail below.
[0202] center part The central portion of the nanostructure comprises monomer residues containing two silicon-carbon bonds with geminal bisphosphonates, hereafter referred to as core monomer residues, which are bonded to each other and to the anchor layer monomer residues via siloxane bonds, Si-O-Si.
[0203] The central portion of the nanostructure comprises a monomer residue according to formula (I): TIFF2025513684000011.tif55170 formula, - Each R 1 , R 2 , R 3 , R4 , R 5 , and R 6 is independently selected from the group consisting of H, a negative charge, and a covalent bond; - Each R 7 , R 8 , R 9 , and R 10 is independently selected from the group consisting of H, a negative charge, and lower alkyl; R 7 , R 8 , R 9 , and R 10 At least 95% of all of the groups are H or negatively charged; - n is an integer from 2 to 5; m is an integer from 2 to 5.
[0204] The covalent bond is a covalent bond to the remainder of the polymer structure.
[0205] In one embodiment, n and m are independently 2 or 3. Preferably, n and m are both 3.
[0206] In one embodiment, the molar fraction of core monomer residues in the nanostructure is between 5% and 20%.
[0207] In another embodiment, the molar fraction of core monomer residues in the nanostructure is between 20% and 40%.
[0208] In a further embodiment, the mole fraction of core monomer residues in the nanostructure is greater than 40%.
[0209] In a specific embodiment, the central monomer residue is derived from 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane by hydrolytic condensation polymerization.
[0210] It is advantageous to use high purity monomers for the synthesis of the central portion, particularly monomers that are highly pure with respect to impurities having reactive siloxane groups, which results in the central portion comprising a large proportion, such as greater than 90%, of monomer residues according to formula (I).
[0211] The molar fraction of core monomer residues in the nanostructure is typically between 5% and 58%.
[0212] In order to successfully bind a radionuclide to a nanostructure, the R 7 , R 8 , R 9 , and R 10 Advantageously, a high percentage of all of the R 7 , R 8 , R 9 , and R 10 More than 95% of all are H or negatively charged.
[0213] In one embodiment, the R present in the nanostructure 7 , R 8 , R 9 , and R 10 Less than 10%, such as less than 5%, of all of the are alkyl.
[0214] In addition to the monomer residues according to formula (I) above, the core may contain a proportion of other monomer residues. These may originate from impurities present in the monomers used in the synthesis of the core. These may also originate from monomer residues that are intentionally included in the synthesis of the nanostructure core.
[0215] Impurities present in the monomers used to synthesize the core may include monomers similar to those that result in monomer residues according to formula (I), but that contain only a single silicon. Such impurities may be generated during the synthesis of the core monomer. Other impurities present may include hydrosilylation reagents, as well as decomposition and disproportionation products of hydrosilylation reagents, such as HSi(OR)3, Si(OR)4, H2Si(OR)2, or (RO)3Si-O-Si(OR)3, where R is any of the R groups defined above. 1 , R 2 , R 3 , R 4 , R 5 , and R 6 It is defined in the same way as in the case of
[0216] Monomer residues derived from monomers intentionally included in the synthesis of the nanostructure core can include, for example, silylated dyes.
[0217] The core may also contain some amount of reaction solvent irreversibly or essentially irreversibly incorporated into the core, particularly when a polyol is used as the reaction solvent for the synthesis of the core. When ethylene glycol is used as the reaction solvent for the synthesis of the core, up to a few percent (w / w basis) of ethylene glycol may be irreversibly incorporated into the core.
[0218] Anchor Layer The nanostructures of the present disclosure include an anchor layer, which improves the bond between the inner portion (core) and the outer portion (coating) of the nanostructure compared to nanostructures that do not have an anchor layer.
[0219] The anchor layer of the nanostructure comprises a monomer residue comprising two silicon atoms connected via a hydrocarbon linker, hereafter referred to as the anchor layer monomer residue, in which the two silicon atoms are separated by one or two carbon atoms.
[0220] The anchor layer monomer residues are bonded to each other, to the monomer residues in the central portion of the nanostructure, and to the monomer residues of the coating layer via siloxane bonds.
[0221] The anchor layer surrounds the central portion (core) of the nanostructure and comprises monomer residues according to formula (II): TIFF2025513684000012.tif32170 formula, - Each R 11 , R 12 , R 13 , R 14 , R 15 , and R 16 is independently selected from the group consisting of H, a negative charge, and a covalent bond; - p is 1 or 2.
[0222] The covalent bond is a covalent bond to the remainder of the polymer structure.
[0223] In one embodiment, p is 1.
[0224] In another embodiment, p is 2.
[0225] Preferably, p is 1.
[0226] The molar fraction of core monomer residues in the nanostructure is typically between 39% and 93%.
[0227] In one embodiment, the molar fraction of anchor layer monomer residues in the nanostructure is between 39% and 60%.
[0228] In another embodiment, the molar fraction of anchor layer monomer residues in the nanostructure is between 60% and 80%.
[0229] In a further embodiment, the mole fraction of anchor layer monomer residues in the nanostructure is greater than 80%.
[0230] In a specific embodiment, p is 1 and the molar fraction of anchor layer monomer residues in the nanostructure is between 60% and 80%.
[0231] In a specific embodiment, the monomer residues of the anchor layer are derived from bis(triethoxysilyl)methane by hydrolytic condensation polymerization.
[0232] Like the core, the anchor layer may also contain a proportion of monomer residues other than those conforming to formula (II). Such monomer residues may include those containing only one silicon atom, such as Si(OR)4 or MeSi(OR)3.
[0233] The thickness of the anchor layer can be estimated from the primed nanostructures used as intermediates in the production of the coated nanostructures. Thus, half the difference between the hydrodynamic diameter of the primed nanostructure and the hydrodynamic diameter of the core nanostructure used to synthesize the primed nanostructure is a convenient estimate of the thickness of the anchor layer. The thickness of the anchor layer of the coated nanostructures can also be estimated from the particle size, density, and detailed composition.
[0234] Preferably, the thickness of the anchor layer is 0.6 to 5 nm, such as 1 to 4 nm, such as 1.1 to 3 nm, such as 1.2 to 2 nm, such as 1.3 to 1.8 nm.
[0235] When a coating monomer having a reactive group at one end of the coating molecule reacts with a reactive group on the surface of an uncoated nanostructure (e.g., a core nanostructure without an anchor layer, also referred to as the central portion), the connection between the coating and the inner portion of the nanostructure (e.g., a core nanostructure without an anchor layer, also referred to as the central portion) forms a region where a particular type of chemical moiety is predominantly present. However, such a region is not the same as the anchor layer as described in this disclosure.
[0236] The thickness of the chemical region consisting of atoms remaining from the reaction of reactive groups on the coating monomer with reactive groups on the surface of the uncoated nanostructure not including the anchor layer (i.e., the core nanostructure, also referred to as the central portion) is significantly less than the thickness of the anchor layer described herein. For example, the ... 45 The linkage between the coating derived from the 1,2-dimethyl-2,4-trimethylheptane consists of a C-Si-O-Si-C moiety. Such a moiety, even in a fully extended configuration, is 6 Å (0.6 nm) or less. Thus, the thickness of the region including the portion connecting the inner portion (i.e., the center portion) of the coated nanostructure to the coating is 6 Å (0.6 nm) or less. This is significantly less than the total thickness of the region including (1) the portion connecting the center portion to the anchor layer, (2) the anchor layer, and (3) the portion connecting the anchor layer to the coating as described in this disclosure.
[0237] Nanostructures according to the present disclosure, i.e., nanostructures including an anchor layer, are much less prone to aggregation than nanostructures in which the same coating monomers are grafted directly onto the core nanostructure, as shown in Example 24, where the resulting nanostructures are not stable with respect to aggregation in the presence of 2 mM calcium ions, and therefore nanostructures without an anchor layer are not suitable for pharmaceutical applications.
[0238] Coating Layer The coating layer comprises a monomer residue having two polyethylene glycol groups and two silicon atoms connected via a hydrocarbon linker, hereafter referred to as the coating monomer residue.
[0239] The coating monomer residues are bonded to each other and to the anchor layer monomer residues via siloxane bonds.
[0240] The coating monomer residue comprises a polyethylene glycol group. As known to those skilled in the art, polymers synthesized by most methods are not identical chemical entities, but rather comprise multiple polymer molecules with different degrees of polymerization. The degree of polymerization can be expressed as the number of monomer residues in the polymer, or alternatively, as the chain length or by the molecular weight of the polymer. The polyethylene glycol groups of the present disclosure are present as a mixture of polyethylene glycol groups with different degrees of polymerization, unless otherwise specified.
[0241] The coating layer surrounds the anchor layer and comprises a monomer residue according to formula (III): TIFF2025513684000013.tif51170 formula, - Each R 17 , R 18 , R 19 , R 20 , R 21 , and R 22 is independently selected from the group consisting of H, a negative charge, and a covalent bond; - q is an integer from 2 to 5; - r is an integer from 2 to 5; - Each R 23 and R 24 is independently selected from the group consisting of H and lower alkyl; - s is an integer from 30 to 105; - t is an integer from 30 to 105.
[0242] The covalent bond is a covalent bond to the remainder of the polymer structure.
[0243] Preferably, q and r are both 3.
[0244] In some cases, s and t are both between 35 and 80, or both between 40 and 70, or both between 45 and 65.
[0245] Preferably, s and t are both from 35 to 55, or both from 45 to 65, or both from 60 to 80. Even more preferably, s and t are both from 35 to 55.
[0246] Preferably, R 23 and R 24 are each methyl or ethyl. Even more preferably, R 23 and R 24 are all methyl.
[0247] In one embodiment, q and r are both 3, s and t are both 35 to 55, and R 23 and R 24 are all methyl.
[0248] The molar fraction of the coating monomer residue in the nanostructure is typically 1% to 4.5%, and preferably 2% to 3.5%.
[0249] In a specific embodiment, s and t are each 35 to 55, and R 23 and R 24 are all methyl, and the molar fraction of the coating monomer residues in the nanostructure is 2% to 3.5%.
[0250] In a specific embodiment, the monomer residues of the coating layer are formed by hydrolysis condensation polymerization of 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45 -methyl)heptane.
[0251] As in the case of the core and anchor layers, they may contain a certain proportion of monomer residues other than those according to formula (III). Impurities present in the monomers used in the synthesis of the coating layer may include monomers similar to those which result in monomer residues according to formula (III) but which contain only a single silicon or only a single polyethylene glycol chain.
[0252] Other components of nanostructures Because all substructures of the nanostructure may contain monomer residues other than those according to formulas (I), (II), and (III), the sum of the mole fractions of monomer residues according to formula (I), (II), and (III) may be less than 1. This may result from the use of non-pure monomeric starting materials or may result from the intentional inclusion of monomers other than those resulting in monomer residues according to formulas (I), (II), and (III).
[0253] Impurities related to the hydrosilylation process cannot be attributed to a specific moiety because the core monomers, anchor layer monomers, and coating layer monomers may all contain similar or identical impurities introduced by the hydrosilylation process used to synthesize the monomers.
[0254] Specific embodiments of nanostructures In a specific embodiment, the molar fraction of core monomer residues according to formula (I) in the nanostructure is between 20% and 40%, and the molar fraction of anchor layer monomer residues according to formula (II) in the nanostructure is between 60% and 80%.
[0255] In a specific embodiment, the molar fraction of core monomer residues according to formula (I) in the nanostructure is between 20% and 40%, and the molar fraction of coating monomer residues according to formula (III) in the nanostructure is between 2% and 3.5%.
[0256] In another specific embodiment, at least 70%, such as at least 80%, such as at least 90%, such as at least 95%, of the monomers in the central portion (core) are monomer residues according to formula (I).
[0257] In another specific embodiment, at least 70%, such as at least 80%, such as at least 90%, such as at least 95%, of the monomer residues in the anchor layer are monomer residues according to formula (II).
[0258] In another specific embodiment, at least 70%, such as at least 80%, such as at least 90%, such as at least 95%, of the monomer residues in the coating layer are monomer residues according to formula (III).
[0259] In another specific embodiment, at least 70% of the monomers in the central portion (core) are monomer residues according to formula (I), at least 70% of the monomer residues in the anchor layer are monomer residues according to formula (II), and at least 70% of the monomer residues in the coating layer are monomer residues according to formula (III).
[0260] In one embodiment, the average number of bonds per monomer residue with other monomer residues is 3-5.
[0261] In another embodiment, the average number of bonds per monomer residue to other monomer residues is greater than 3.5, such as greater than 4, such as greater than 4.5.
[0262] In a specific embodiment, the monomer residues of the core portion are derived from 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane by hydrolytic condensation polymerization, the monomer residues of the anchor layer are derived from bis(triethoxysilyl)methane by hydrolytic condensation polymerization, and the monomer residues of the coating layer are derived from 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45 -methyl)heptane.
[0263] Chelation The nanostructures according to the present disclosure are strong chelators of multivalent metal ions. This makes them suitable as carriers of radionuclides for medical purposes, such as imaging or cancer treatment. It is important that the radionuclide is strongly bound to the carrier in order to minimize unwanted off-target accumulation of the radionuclide in vivo.
[0264] The nanostructures of the present disclosure have the advantage that essentially all of the radionuclides remain bound to the nanostructure in vivo, an example of which is shown in Example 16.
[0265] More than 100 chelating groups in the form of geminal bisphosphonate groups are distributed in the central part of the nanostructure. The chelating groups may be considered to be randomly distributed throughout the central part, or may depend on chance for the arrangement of the chelating groups to allow for the preferred chelation of metal ions by multiple chelating groups. In the case of chance dependence, it is necessary to incorporate a large excess of chelating groups in the central part in order to obtain a reasonable probability of forming a cluster of chelating groups with strong binding affinity.
[0266] The phosphonate group in ester form is i.e. R 7 , R 8 , R 9 , and R 10 is alkyl, it is generally preferred to have R in the monomer residue according to formula (I) rather than the acid or ionized form of the phosphonate group. 7 , R 8 , R 9 , and R 10 However, the binding with metal ions is weaker than that with H or negative charge, respectively. Therefore, in order to strongly bind radioisotopes to nanostructures, R present in the nanostructures is 7 , R 8 , R 9 , and R 10 Advantageously, a large proportion of all of the groups, such as more than 90% or even more than 95%, are H or negatively charged.
[0267] In the synthesis of nanostructures, R 7 , R 8 , R 9 , and R 10 The reaction conditions that result in highly crosslinked nanostructures also result in nanostructures in which most of the phosphonate groups have been hydrolyzed, i.e., intermediates in which R is alkyl are used. 7 , R 8 , R9 , and R 10 It has been found that this also results in nanostructures in which the groups are H or negatively charged.
[0268] Example 8 provides NMR data supporting the essentially complete hydrolysis of the phosphonate in nanostructures according to the present disclosure.
[0269] How strongly nanostructures bind to metal ions is not easily quantified by directly measuring the binding constant between the nanostructures and metal ions, but is most conveniently determined by competitive chelation. Examples 9 and 11 show that nanostructures according to the present disclosure are good chelators of multivalent metal ions by competitive chelation with EDTA, a known chelator. Example 16 shows that nanostructures also bind strongly to metal ions in vivo.
[0270] Further advantages of nanostructures according to the present disclosure It is known in the art that nanostructures are often prone to aggregation, which can reduce the shelf life of products containing the nanostructures, as the aggregated nanostructures often have significantly different properties than the individual nanostructures.
[0271] Nanostructures according to the present disclosure have the advantage that they are highly resistant to aggregation, even when stored for long periods under harsh conditions, and Example 17 shows that nanostructures according to the present disclosure show no signs of aggregation even when stored at 60° C. for over a month.
[0272] Nanostructures according to the present disclosure are highly water soluble, with Example 15 showing an example where samples of nanostructures up to about 25% (wt / vol) showed no signs of aggregation.
[0273] High solubility is advantageous in processing nanostructures by allowing processing with relatively smaller volumes of solution, especially at large scales where the amounts of dilute solution can be enormous.
[0274] Nanostructures according to the present disclosure are biocompatible. Examples 12, 13, 14, and 16 demonstrate that the nanostructures can be injected into mammals without causing substantial adverse reactions.
[0275] For a nanostructure to have time to distribute into tumor tissue, it must be present in the bloodstream for a long enough time, in other words, it must be stable under physiological conditions for a sufficient time to be distributed to the target site.
[0276] The nanostructures of the present disclosure are long-circulating, i.e., a sample injected intravenously will remain in the blood for an extended period of time. The plasma half-life, t 1 / 2 is long enough to allow the nanostructures to accumulate in large amounts in tumors in tumor-bearing mouse models.
[0277] In Examples 12, 13, 14, and 16, the nanostructures were shown to reduce plasma t 1 / 2 It is shown that the
[0278] A comparison of nanostructures according to the present disclosure with reference nanostructures outside the scope of the present disclosure is provided in Example 20. Nanostructures according to the present disclosure have a much longer plasma half-life.
[0279] For nanostructures to be suitable as carriers of radionuclides for cancer imaging or treatment, the nanostructures must accumulate in tumor tissue.
[0280] The nanostructures of the present disclosure accumulate in tumor tissue. Example 12 shows that a few percent of the injected dose accumulates in tumors in tumor-bearing mouse models, corresponding to 10%-20% of the injected dose per gram of tumor tissue.
[0281] Compared to the nanostructures disclosed in WO 2015 / 144891, the nanostructures of the present disclosure offer several improvements. Specifically, the nanostructures of the present disclosure have greatly improved pharmacokinetics (see Example 16) and plasma half-life (see Example 21) is several times longer than the nanostructures disclosed in WO 2015 / 144891. Furthermore, the nanostructures of the present disclosure have much better stability and longer shelf life (see Example 23). The nanostructures of the present disclosure also bind radionuclides more strongly than the nanostructures described in WO 2015 / 144891.
[0282] Synthesis of Nanostructures According to the Present Disclosure The nanostructures of the present disclosure can be synthesized by a series of hydrolysis-condensation polymerization reactions of monomers containing two trialkoxysilane groups. In particular, it has been found that the polymerization of a precursor having two triethoxysilyl groups is particularly suitable for the synthesis of nanostructures.
[0283] The synthesis of the nanostructure includes the steps of synthesizing a central portion of the nanostructure (also referred to as a core nanostructure), adding or grafting an anchor layer onto the central portion to form a primed nanostructure, and adding or grafting a coating layer onto the primed nanostructure to form a nanostructure according to the present disclosure.
[0284] Preferably, the nanostructures are synthesised using core nanostructures having an average hydrodynamic diameter of 14 to 25 nm, or 15 to 21 nm, or 16 to 19 nm.
[0285] Preferably, the nanostructures are synthesized using a primed nanostructure having an anchor layer having a thickness of 0.6 to 5 nm, such as 1 to 4 nm, such as 1.1 to 3 nm, such as 1.2 to 2 nm, such as 1.3 to 1.8 nm.
[0286] Preferably, the nanostructures are synthesized using a core nanostructure having an average hydrodynamic diameter of 15-21 nm and an anchor layer having a thickness of 1.1-3 nm.
[0287] Synthesis of the central part The central portion of the nanostructure can be synthesized by hydrolytic condensation polymerization of a core monomer having a structure according to formula (IV): TIFF2025513684000014.tif53170, R 25 ~R 34 is independently selected at each occurrence to be lower alkyl; u is an integer from 2 to 5; and v is an integer from 2 to 5.
[0288] R 25 ~R 30 is ethyl, and R 31 ~R 34 It is particularly useful to use monomers where is methyl and u and v are both 3.
[0289] The synthesis involves dissolving the core monomer in a mixture of water and a lower alcohol and heating the resulting solution for a time period depending on the solvent composition and temperature. Preferably, the solvent is 80%-90% (vol / vol) aqueous ethylene glycol, the reaction temperature is 120°C-150°C, and the reaction time is 30-400 hours.
[0290] Under such reaction conditions, the size of the nanostructures stabilizes after a certain time at a size that depends on the reaction conditions.
[0291] For a given reaction solvent and reaction temperature, the particle size of the resulting nanostructures can be controlled by the concentration of monomer in the initial reaction mixture. Example 4 shows how the particle size of the core nanostructures can be varied by varying the monomer concentration in solution.
[0292] It is advantageous to use monomers of high purity for the synthesis of the core nanostructures, and purity, especially with respect to oligomers, appears to be important for reproducible synthesis of core nanostructures.
[0293] In Examples 1A, 2A, and 3A, different realizations of the synthesis of the core part of the nanostructures are presented.
[0294] Synthesis of anchor layer The anchor layer is added to the central portion of the nanostructure by reaction of the central portion of the nanostructure with an anchor layer monomer according to formula (V): TIFF2025513684000015.tif29170, R 35 ~R 40 is independently selected at each occurrence to be lower alkyl; and w is 1 or 2.
[0295] Preferably, R 35 ~R 40 is ethyl.
[0296] Preferably, w is 1.
[0297] R 35 ~R 40 It is particularly useful to use monomers where is ethyl and w is 1.
[0298] Examples 1B, 2B, and 3B show different implementations of the addition of an anchor layer to the central portion.
[0299] The addition of the anchor layer can be achieved by contacting the core nanostructure with the anchor layer monomer in the solvent mixture of the core nanostructure synthesis at a temperature of 80°C to 130°C for 1 to 24 hours, resulting in a solution of primed nanostructures.
[0300] In many cases, the anchor layer monomer is not completely soluble in the solvent mixture used in the synthesis of the core portion. Therefore, it is advantageous to finely disperse the anchor layer monomer in the reaction medium by vigorously stirring the reaction mixture at an elevated temperature. Under such treatment, the anchor layer monomer is quickly partially hydrolyzed, such as within 15 minutes, such as within 30 minutes, and the partially hydrolyzed anchor layer monomer dissolves in the reaction medium.
[0301] It is often convenient to calculate the amount of anchor layer monomer in terms of equivalents relative to the amount of core monomer used to synthesize the core nanostructure solution.
[0302] Typically, 1 to 10 equivalents of the anchor layer monomer are used.
[0303] Coating layer synthesis The coating layer is added to the primed nanostructure by reaction of the primed nanostructure with a coating layer monomer according to formula (VI): TIFF2025513684000016.tif46170, R 41 ~R 46 are each independently selected to be lower alkyl; x is an integer from 2 to 5; y is an integer from 2 to 5; z and za are independently from 30 to 105; R 47 and R 48 are each independently selected from the group consisting of H and lower alkyl.
[0304] Preferably, R 41 ~R 46 is ethyl.
[0305] Preferably, x and y are both 3.
[0306] Preferably, R 47 and R 48 are all methyl.
[0307] R 41 ~R 46 is ethyl, x and y are both 3, R 47 and R 48 It has been found to be particularly useful to use monomers in which:
[0308] Examples 1C, 2C, 3C, 6A, and 6B provide some examples of the addition of coating layers to primed core nanostructures.
[0309] The addition of the coating layer is most conveniently accomplished by adding the coating layer monomer to a solution of the primed nanostructures in the solvent mixture used for the synthesis of the primed nanostructures. It is often advantageous to perform the addition of the coating layer at a higher dilution than the synthesis of the core or the synthesis of the primed nanostructures.
[0310] It is often advantageous to add the coating layer monomer to the solution of primed nanostructures gradually, such as by adding multiple portions or slowly pouring the solution of the coating layer monomer.
[0311] The addition of the coating layer is preferably carried out at an elevated temperature, such as above 100°C, such as 110°C.
[0312] The reaction time for adding the coating layer is typically 20 to 100 hours.
[0313] It is often convenient to calculate the amount of coating layer monomer in terms of equivalents relative to the amount of core monomer used to synthesize the solution of primed nanostructures.
[0314] Typically, 0.5 to 5 equivalents of coating layer monomer are used.
[0315] The solution at the end of the addition of the coating layer contains the above-mentioned nanostructures, the organic solvent, and various molecular impurities. In order for the nanostructures to be useful as carriers of radionuclides for pharmaceutical purposes, they must be present as an aqueous solution. The reaction solvent can be exchanged with water by ultrafiltration. Using a filtration membrane with an appropriate cutoff, such as 100 kDa or more, such as 300 kDa or more, such as 1,000 kDa or more, such as 10,000 kDa or more, such as 100,000 kDa or more, such as 1,000,000 kDa or more, allows the removal of molecular impurities from the nanostructure solution at the same time as the solvent exchange.
[0316] It has been found advantageous to use tangential flow filtration for solvent exchange and removal of molecular impurities.
[0317] Specific synthetic routes for the synthesis of nanostructures according to the present disclosure Preferably, the central portion (also referred to as the core nanostructure) is synthesized by heating a solution of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane in aqueous ethylene glycol, such as by heating a 20 mM to 100 mM solution of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane in 80% (volume / volume) aqueous ethylene glycol for 40 to 400 hours. or by heating a 20 mM to 60 mM solution of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane in 90% (volume / volume) aqueous ethylene glycol to a temperature of 130° C. to 150° C. for 30 to 100 hours; or by heating a 30 mM to 40 mM solution of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane in 90% (volume / volume) aqueous ethylene glycol to a temperature of 135° C. to 145° C. for 40 to 60 hours.
[0318] Preferably, the primed nanostructures are synthesized by heating a solution of the core nanostructure formed from 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane with 1-5 equivalents of bis(triethoxysilyl)methane, such as by heating a solution of the core nanostructure formed from 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane with 2-3 equivalents of bis(triethoxysilyl)methane at a temperature of 90° C. to 140° C. for 2-12 hours.
[0319] Preferably, the coating layer monomer is 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45 -methyl)heptane.
[0320] R in formula (VI) 41 ~R 46 When is ethyl, the coating layer monomer is conveniently added to the solution of primed nanostructures by slowly injecting a solution of the coating layer monomer in ethanol.
[0321] Nanostructures containing radionuclides The nanostructures according to the present disclosure described above having one or more radioisotopes bound to the core portion of the nanostructure are suitable for use in imaging and / or treating cancer. The radionuclides are strongly bound to the nanostructure.
[0322] Strongly bound radionuclides are advantageous for pharmaceutical applications. Weakly bound radionuclides will dissociate to some extent from the nanostructure and may bind to endogenous compounds, which may result in a mismatch between the distribution of the radionuclide in the organism and that of the nanostructure, potentially resulting in an increase in unwanted radiation-related side effects and even a decrease in tumor-targeted radiation.
[0323] Since the coordination chemistry of different isotopes of the same element is the same, some realizations of radionuclide-bound nanostructures are shown as examples using non-radioactive isotopes (also called "cold" isotopes) of the element of interest. Nanostructures containing radioisotopes are conveniently synthesized by mixing a solution of nanostructures according to the present disclosure with a solution of a salt of the radionuclide, preferably according to the method described below. If the radiolabeled nanostructures are to be used for pharmacological purposes, the salt of the radionuclide should be a pharma- ceutically acceptable salt.
[0324] Specific methods for radiolabeling of nanostructures are described below.
[0325] In Examples 9, 10, and 11, the cold equivalents of nanostructures loaded with Lu, Sm, Y, Gd, Eu, Tb, Zr, Ho, Pr, and Ga are shown.
[0326] In Examples 13 and 14, the radionuclide lutetium-117( 177 The realization of nanostructures loaded with ZnO (Lu) is presented.
[0327] Typically, the plurality of nanostructures carries an average of 0.01 to 2 radioisotopes per nanostructure, such as 0.5 to 1 radioisotope per nanostructure.
[0328] In a specific embodiment, the plurality of nanostructures carries an average of 0.01 to 1 radioisotope per nanostructure.
[0329] In another specific embodiment, the plurality of nanostructures carries an average of 0.5 to 2 radioisotopes per nanostructure.
[0330] Preferably, the average hydrodynamic diameter of the plurality of nanostructures is 25 to 35 nm.
[0331] The radionuclide may be a radionuclide suitable for imaging, such as PET imaging or SPECT imaging.
[0332] The radionuclide may be a radionuclide suitable for radiotherapy and / or imaging.
[0333] In one embodiment, the nanostructures have an average hydrodynamic diameter of 25-35 nm, and the nanostructures chelate a radionuclide for PET imaging. The radionuclide for PET imaging is gallium-68 ( 68 Ga).
[0334] In another embodiment, the average hydrodynamic diameter of the plurality of nanostructures is between 25 and 35 nm, and the nanostructures chelate a radionuclide for SPECT imaging. The radionuclide for SPECT imaging is technetium-99m in the form of a trivalent cation ( 99m Tc 3+ ).
[0335] In a further embodiment, the plurality of nanostructures have an average hydrodynamic diameter of 25-35 nm, and the nanostructures chelate a radionuclide for radiation therapy.
[0336] In one embodiment, the average hydrodynamic diameter of the plurality of nanostructures is 25-35 nm, and the nanostructures are made of yttrium-90 ( 90 Y) to chelate.
[0337] In one embodiment, the nanostructures have an average hydrodynamic diameter of 25-35 nm, and the nanostructures chelate a radionuclide for imaging and / or radiotherapy. The radionuclide for imaging and / or radiotherapy is lutetium-177 ( 177 Lu).
[0338] In another embodiment, the average hydrodynamic diameter of the plurality of nanostructures is 25-35 nm, the molar fraction of core monomer residues in the nanostructures is 20%-40%, the molar fraction of anchor layer monomer residues in the nanostructures is 60%-80%, the molar fraction of coating monomer residues in the nanostructures is 2%-3.5%, and the nanostructures are lutetium-177( 177 On average, 0.5 to 2 radionuclide ions for imaging and / or radiotherapy, such as 1Lu, are chelated per nanostructure.
[0339] In one embodiment, the average hydrodynamic diameter of the plurality of nanostructures is 25-35 nm, and the nanostructures are comprised of samarium-153( 153 3. Chelate radionuclides for imaging and / or radiotherapy such as Sm).
[0340] Pharmaceutical compositions containing nanostructures The present disclosure further relates to a pharmaceutical composition comprising a plurality of spherical nanostructures according to the present disclosure, water, and at least one excipient.
[0341] At least one excipient may be an antioxidant or a cryoprotectant. The antioxidant is preferably thioglycerol and / or gentisic acid. The cryoprotectant is preferably glycerol.
[0342] One of the antioxidants selected for acidic injection solutions is sodium metabisulfite. Sodium metabisulfite inhibits the degradation of nanostructures due to oxidation of polyethylene glycol chains in the coating layer. Surprisingly, it has been found that sodium metabisulfite is a poorly suited excipient for the formulation of nanostructures according to the present disclosure, since sodium metabisulfite interferes with the binding of metal ions to the nanostructures. Example 11 shows a comparison of the metal binding power of nanostructures in the presence and absence of sodium metabisulfite, showing that the presence of sodium metabisulfite more than doubles the amount of Lu extracted from the nanostructures by competitive chelation with EDTA.
[0343] In one embodiment, the pharmaceutical composition comprises an antioxidant, preferably thioglycerol and / or gentisic acid.
[0344] In one embodiment, the pharmaceutical composition comprises an antioxidant other than a sulfite or ascorbate.
[0345] In another embodiment, the pharmaceutical composition comprises a cryoprotectant.
[0346] In one embodiment, the pharmaceutical composition comprises an oxidizing agent and a cryoprotectant.
[0347] In one embodiment, the pharmaceutical composition comprises thioglycerol.
[0348] In another embodiment, the pharmaceutical composition comprises gentisic acid.
[0349] In a further embodiment, the pharmaceutical composition comprises glycerol.
[0350] In yet another embodiment, the pharmaceutical composition comprises thioglycerol and gentisic acid.
[0351] In another embodiment, the pharmaceutical composition comprises thioglycerol, gentisic acid, and glycerol.
[0352] Thus, the pharmaceutical composition comprises a solution containing the nanostructures, the nanostructures being as described above. For simplicity and clarity, this solution will be referred to hereinafter as the "carrier formulation."
[0353] Depending on the application of the pharmaceutical composition, the nanostructures may be "empty nanostructures", i.e., they do not carry any chelated ions, or they may be "loaded nanostructures", i.e., they carry polyvalent metal ions. The polyvalent metal ions may be radioisotopes (radionuclides) or non-radioactive polyvalent metal ions.
[0354] Pharmaceutical Compositions Comprising "Empty" Nanostructures Where the medicament comprises "empty" nanostructures, the carrier formulation is preferably formulated to be suitable for storage and shipping, and for later combination with a radioisotope to form an injectable formulation suitable for injection into a living organism, such as a human, for the purposes of imaging and / or treating a condition, such as cancer.
[0355] The carrier formulation comprises an acidic solution of the nanostructures, water, and at least one excipient as described below.
[0356] The carrier formulation has a low pH, as required by the radiolabeling methods described below, and preferably has a pH of 1.5 to 2.5.
[0357] In a preferred embodiment, the formulation comprises thioglycerol, gentisic acid, and glycerol. In such a formulation, thioglycerol and gentisic acid function as antioxidants and glycerol functions as a cryoprotectant. Such a formulation has the advantages of greatly extending the shelf life of the nanostructures, allowing storage of the solution as a frozen solution, and not interfering with radiolabeling of the nanostructures.
[0358] The nanostructures according to the present disclosure include polyethylene glycol chains. When the polyethylene glycol chains in the nanostructures are oxidized, free polyethylene glycol chains are formed in the solution. The presence of such molecular degradation products in the solution may make the solution unsuitable for medical use, and the occurrence of molecular degradation products therefore shortens the shelf life of the nanostructure solution. Formulating the carrier formulation as described above has the advantage of significantly extending the shelf life of the nanostructures by suppressing the formation of molecular degradation products formed by the oxidation of the polyethylene glycol chains in the coating layer of the nanostructures. Example 17 shows that the nanostructure solution formulated according to the present disclosure has an extended shelf life.
[0359] Nanostructures formulated with thioglycerol and gentisic acid can be radiolabeled in the manner described below without increasing the amount of radionuclide that can be extracted from the nanostructure by competitive chelation with EDTA. Nanostructures formulated with thioglycerol and gentisic acid further do not risk producing calcium oxalate precipitates when administered to a patient along with calcium (see below for a discussion regarding the presence of calcium in pharmaceutical compositions used for intravenous administration of nanostructures).
[0360] The shelf life of pharmaceutical compositions can often be extended by freezing and storing at low temperatures. However, freezing and thawing a solution of nanostructures according to the present disclosure in pure water causes significant aggregation of the nanostructures, making them unsuitable for pharmaceutical use. Formulating a carrier formulation according to the present disclosure has the advantage of allowing the solution to be frozen, thereby greatly extending the shelf life of the nanostructures. Examples 1E, 1F, and 18 show that the nanostructure solutions formulated according to the present disclosure can be frozen and stored as frozen solutions. Formulating a carrier formulation also has the advantage that the frozen solutions can be stored in normal freezers, such as at about -20°C, and that freezing the solutions does not require flash freezing.
[0361] In one embodiment, the pharmaceutical composition comprises an antioxidant.
[0362] In one embodiment, the pharmaceutical composition comprises an antioxidant other than a sulfite or ascorbate.
[0363] In another embodiment, the pharmaceutical composition comprises a cryoprotectant.
[0364] In one embodiment, the pharmaceutical composition comprises an oxidizing agent and a cryoprotectant.
[0365] In one embodiment, the pharmaceutical composition comprises thioglycerol.
[0366] In another embodiment, the pharmaceutical composition comprises gentisic acid.
[0367] In a further embodiment, the pharmaceutical composition comprises glycerol.
[0368] In yet another embodiment, the pharmaceutical composition comprises thioglycerol and gentisic acid.
[0369] In another embodiment, the pharmaceutical composition comprises thioglycerol, gentisic acid, and glycerol.
[0370] In one embodiment, the pharmaceutical composition has a pH of less than 3.5, such as less than 2.5, such as less than 3. Such a pharmaceutical solution is suitable for storage.
[0371] In a specific embodiment, the pharmaceutical composition has a pH of less than 3.5 and comprises thioglycerol, gentisic acid, and glycerol.
[0372] In another embodiment, the pharmaceutical composition comprises thioglycerol from 0.01 mg / ml to 100 mg / ml, such as 0.1 mg / ml to 10 mg / ml thioglycerol, such as 0.2 mg / ml to 2 mg / ml thioglycerol.
[0373] In a further embodiment the pharmaceutical composition comprises 0.01 mg / ml to 100 mg / ml of gentisic acid, such as 0.03 mg / ml to 3 mg / ml of gentisic acid, such as 0.1 mg / ml to 1 mg / ml of gentisic acid.
[0374] In another embodiment, the pharmaceutical composition comprises from 1 mg / ml to 500 mg / ml of glycerol, such as from 3 mg / ml to 300 mg / ml of glycerol, such as from 10 mg / ml to 100 mg / ml of glycerol.
[0375] In a specific embodiment, the pharmaceutical composition has a pH of less than 3.5 and contains 0.1 mg / ml to 10 mg / ml thioglycerol, 0.03 mg / ml to 3 mg / ml gentisic acid, and 3 mg / ml to 300 mg / ml glycerol. Such a pharmaceutical composition containing "empty" nanostructures can be used as the solution in step a) of the method for radiolabeling nanostructures described below. Such a pharmaceutical composition containing "empty" nanostructures can also constitute the aqueous solution of spherical nanostructures in the kit described below.
[0376] Pharmaceutical Composition for Intravenous Administration The nanostructures according to the present disclosure are potent chelators of calcium. Thus, injection of the nanostructures without co-administration of an adequate amount of calcium can adversely affect functions, such as cardiac function, in patients that depend on calcium ion concentrations in the blood. Thus, use of the injectable nanostructures must be accompanied by an injection of calcium. The nanostructures and calcium may be administered together in a single injection or infusion.
[0377] One of the antioxidants selected for acidic injection solutions is ascorbic acid. Ascorbic acid is known to produce oxalic acid upon decomposition. In injection solutions, oxalic acid and calcium are incompatible, since calcium oxalate is highly insoluble and prone to form precipitates. This is especially true at neutral or slightly basic pH, such as that found in blood, where there is a risk of calcium oxalate precipitates forming in the patient's bloodstream. Therefore, ascorbic acid or ascorbate salts are not suitable for the formulation of nanostructures according to the present disclosure. Therefore, other antioxidants, such as thioglycerol and gentisic acid, are preferably used, because they do not pose the risk of producing calcium oxalate precipitates when administered to a patient together with calcium.
[0378] Briefly, a pharmaceutical composition for intravenous administration comprises a plurality of spherical nanostructures according to the present disclosure, water, and at least one excipient. The pharmaceutical composition for intravenous administration may further comprise 0.1-10 mg / ml thioglycerol, 0.03-3 mg / ml gentisic acid, and 3-300 mg / ml glycerol. The pharmaceutical composition for intravenous administration may further comprise a chelated metal ion. The pH of such pharmaceutical composition is essentially neutral.
[0379] In a specific embodiment, in the pharmaceutical composition, the average hydrodynamic diameter of the plurality of nanostructures is 25-35 nm, the molar fraction of the core monomer residues in the nanostructure is 20%-40%, the molar fraction of the anchor layer monomer residues in the nanostructure is 60%-80%, the molar fraction of the coating monomer residues in the nanostructure is 2%-3.5%, and the nanostructure is lutetium-177( 177 The nanostructure chelates an average of 0.5 to 2 radionuclide ions for imaging and / or radiotherapy, such as 100000000000001 Lu). The pharmaceutical composition is preferably contained in a vial or syringe. The pH of such a pharmaceutical composition is essentially neutral. Such a pharmaceutical composition is suitable for injection.
[0380] Medical uses of nanostructures and compositions comprising nanostructures according to the present disclosure Nanostructures according to the present disclosure and pharmaceutical compositions comprising such nanostructures can be used in a variety of applications, as described below.
[0381] Use of Nanostructures in Radionuclide Therapy or Imaging The present disclosure also relates to the use of nanostructures according to the present disclosure in radionuclide therapy or medical imaging. Often the purpose of such use is the treatment or imaging of cancer.
[0382] Preferably, nanostructures used for radionuclide therapy or medical imaging are radiolabeled using the methods described below and included in the pharmaceutical compositions described above, which may be achieved through the use of the kits described below.
[0383] When nanostructures according to the present disclosure are used to treat cancer, they may be used in combination with external beam radiation therapy and / or in combination with chemotherapy.
[0384] In one embodiment the radionuclide is a PET imaging radionuclide and the application is PET imaging.
[0385] In another embodiment the radionuclide is a radionuclide for SPECT imaging and the application is SPECT imaging.
[0386] In a further embodiment the radionuclide is a radiotherapeutic radionuclide and the application is radionuclide therapy.
[0387] Various radionuclides are described below and in the "Definitions of Terms" section.
[0388] Use of "cold" nanostructures Nanostructures that do not contain radionuclides may be referred to as cold nanostructures, similar to nanostructures that contain radionuclides, which may be referred to as hot nanostructures. Cold nanostructures may either not contain chelated polyvalent metal ions or may be loaded with non-radioactive metal ions.
[0389] Nanostructures can be loaded with non-radioactive metal ions in a manner similar to that described below, except that the salt of the radionuclide is exchanged for a non-radioactive salt.
[0390] As mentioned above, the "empty" cold nanostructures can be used as intermediates in the manufacture of pharmaceutical compositions.
[0391] Nanostructures according to the present disclosure that are free of radionuclides can also be used for pharmaceutical purposes.
[0392] Uses of radionuclide-free nanostructures may include use to induce tolerance to the nanostructures in patients. Nanostructures according to the present disclosure are coated with polyethylene glycol. It is known that some individuals exhibit immune responses to polyethylene glycol, as indicated, for example, by the presence of polyethylene-binding antibodies. Thus, the use of nanostructures containing polyethylene glycol may be complicated in certain patients by immune responses to the nanostructures, for example, anaphylactic reactions upon exposure to the nanostructures or accelerated clearance of the nanostructures from the blood. In such situations, treating a patient with "empty" cold nanostructures may induce tolerance to the nanostructures in the patient, after which the hot nanostructures can be used medicinally.
[0393] Similarly, cold nanostructures can be used to deplete reservoirs of immune system components that react against the nanostructures prior to administration of hot, i.e., radiolabeled, nanostructures. In such cases, rather than inducing tolerance to the nanostructures, the cold nanostructures temporarily deplete the patient's immune system's ability to subsequently administer the hot nanostructures, allowing them to circulate freely.
[0394] The "empty" cold nanostructures according to the present disclosure can also be used as scavengers for multivalent metal ions in patients. Such uses can include the scavenging of toxic metal ions. Example 10 shows that nanostructures according to the present disclosure strongly bind a variety of multivalent cations, with only trace amounts of unbound metal ions. This shows that cold nanostructures can be used to scavenge essentially any multivalent cation.
[0395] Cold nanostructures according to the present disclosure may also be used as contrast agents, in which case the nanostructures may be loaded with metal ions that exhibit additional contrast in imaging modalities, such as gadolinium or manganese for magnetic resonance imaging.
[0396] Method for radiolabeling a plurality of spherical nanostructures The present disclosure also relates to a method for radiolabeling a plurality of spherical nanostructures with a multivalent cationic radionuclide. Notably, the same method steps can be used to load the nanostructures with non-radioactive multivalent metal ions.
[0397] This method is used to load radioisotopes into nanostructures in a novel and effective way, which serves the purpose of minimizing loading time and maximizing dissociation time. The loading time must be short for a practically useful product, especially if the radioisotope has a short lifetime. The dissociation time must be long to avoid the radioisotope leaking out of the nanostructure after injection into the patient and causing undesirable radiotoxicity.
[0398] This method has the advantage that when the radioisotope is loaded onto the nanostructure by this method, the radioisotope binds more strongly to the nanostructure than when conventional loading is used. It has the further advantage that it can be carried out within a few hours, thereby allowing both the preparation and use of the radiolabeled nanostructure to be carried out on the same working day. This method has the further advantage that it can be realised by the use of procedures commonly used in radiopharmacies, as they are carried out in hospitals.
[0399] Chelating phosphonate groups of the type found in the nanostructures of the present disclosure are acidic, i.e., at high pH, they ionize to negatively charged phosphonates. The negatively charged dissociated phosphonate groups are better ligands for metal ions than the corresponding non-ionized forms, and complexation reactions between phosphonate ligands and metal ions are generally advantageously carried out at high pH.
[0400] Surprisingly, it has been found that when nanostructures according to the present disclosure are loaded with polyvalent metal ions at low pH and then the pH is raised to a neutral or near-neutral pH, such as physiological pH, the metal ions bind more strongly to the nanostructures than when the nanostructures are loaded with the metal ions at a more alkaline pH.
[0401] The method of radiolabeling a plurality of spherical nanostructures with a multivalent cationic radionuclide comprises: a) providing a solution having a pH of less than 3.5 and containing a plurality of spherical nanostructures, the solution containing no radionuclides or polyvalent metal ions; and b) contacting the solution of step a) with a pharma- ceutical acceptable salt of a radionuclide; and c) adjusting the pH of the solution to greater than 6; Includes.
[0402] The solution of nanostructures used in step a) preferably has a pH of less than 3, such as less than 2.5. More preferably, the solution has a pH of between 1.5 and 2.5.
[0403] The solution of nanostructures used in step a) is generally an aqueous solution of nanostructures, which may further comprise excipients such as stabilizers, antioxidants, cryoprotectants, preservatives, and antimicrobial agents.
[0404] The pharma- ceutically acceptable salt of the radionuclide used in step b) is typically used as a solution of the radioisotope. Contacting the solution of nanostructures with the radioisotope can be achieved by mixing the solution of nanostructures with a solution of the radioisotope.
[0405] The radionuclide in step b) may be used in an amount of 0.01 to 2 atoms per nanostructure, such as 0.5 to 1 atom of the radionuclide per nanostructure.
[0406] After step b) and before carrying out step c), it is advantageous to incubate the solution for some time. Preferably, this incubation is carried out at a slightly elevated temperature, such as 40° C. to 80° C., such as 50° C. to 70° C., such as 50° C. to 60° C. The incubation time is preferably at least 15 minutes, such as 30 minutes to 3 hours.
[0407] The adjustment of the pH in step c) can be achieved by adding a buffer solution to the solution of nanostructures. It is also envisaged to adjust the pH by the addition of a strong base such as an alkali hydroxide or an alkaline earth metal hydroxide.
[0408] After step c), it is advantageous to incubate the solution for some time before use of the radiolabeled nanostructures. Preferably, this incubation is carried out at a slightly elevated temperature, such as 40° C. to 80° C., such as 50° C. to 70° C., such as 50° C. to 60° C. The incubation time is preferably at least 15 minutes, such as 30 minutes to 3 hours.
[0409] The solution obtained after step c) or after the incubation after step c) can easily be analyzed for chemical and radiochemical purity by methods known to those skilled in the art.
[0410] Implementation of the method with cold equivalents of several radioisotopes is shown in Examples 1F and 10. Implementation of the method with several radioisotopes (also called radionuclides) is shown in Examples 13 and 14.
[0411] Example 9 provides a comparison of the above method with traditional metal loading methods, demonstrating that the disclosed method results in stronger bonds between nanostructures and radioisotopes.
[0412] In one embodiment, the solution of nanostructures in step a) has a pH between 1.5 and 3, such as between 1.9 and 2.5.
[0413] In another embodiment the radionuclide in step b) is used in an amount of 0.01 to 1 atom of the radionuclide per nanostructure.
[0414] In a further embodiment, the radionuclide in step b) is used in an amount of 0.5 to 2 atoms of radioisotope per nanostructure.
[0415] In one embodiment the radionuclide of step b) is suitable for use in PET imaging.
[0416] In another embodiment the radionuclide of step b) is suitable for use in SPECT imaging.
[0417] In a further embodiment, the radionuclide of step b) is suitable for use in radiotherapy.
[0418] In one embodiment, the radionuclide in step b) is gallium-68 ( 68 Ga), technetium-99m in the form of trivalent cation ( 99m Tc 3+ ), Lutetium-177( 177 Lu), Yttrium-90 ( 90 Y), and samarium-153 ( 153 Sm).
[0419] In a specific embodiment, the radionuclide in step b) is gallium-68 ( 68 Ga).
[0420] In another specific embodiment, the radionuclide in step b) is technetium-99m in the form of a trivalent cation ( 99m Tc 3+ ).
[0421] In a further specific embodiment, the radionuclide in step b) is lutetium-177 ( 177 Lu).
[0422] In yet another specific embodiment, the radionuclide in step b) is yttrium-90 ( 90 Y).
[0423] In a further specific embodiment, the radionuclide in step b) is samarium-153 ( 153 Sm).
[0424] In one specific embodiment, the adjustment of the pH in step c) is performed by adding a buffer containing Tris at a pH above 7.5.
[0425] In another specific embodiment, the solution is incubated between steps b) and c) at 50° C. to 70° C. for 30 minutes to 2 hours.
[0426] In a further embodiment, the solution is incubated at 50° C.-70° C. for 1 hour-3 hours after step c) before the radiolabeled nanostructures are used.
[0427] kit The present disclosure also relates to a kit that allows for the realization of radiolabeling of nanostructures according to the present disclosure by the methods disclosed above.
[0428] The kits may be used in radiopharmacy to prepare single or small doses of radiolabeled nanostructures for use in imaging and / or treatment of pathological conditions such as cancer.
[0429] The kits can be used in combination with a radioisotope source to generate radiolabeled nanostructures suitable for intravenous use.
[0430] The kit comprises an aqueous solution of spherical nanostructures according to the present disclosure essentially free of radionuclides or polyvalent metal ions, having a pH of less than 3.5, an aqueous solution of a pharma- ceutically acceptable buffer having a pH of at least 6, and instructions for use to enable the radiolabeling method described above to be carried out.
[0431] Kits may optionally include mixing containers, equipment for sterile filtration, pharma- ceutically acceptable diluents, centrifugal filters, and / or equipment for shielding from ionizing radiation.
[0432] The kit comprises a volume of an aqueous solution of the above-described spherical nanostructures, having a pH of less than 3.5, contained in a suitable container, such as a pharmaceutical glass vial with a rubber cap, the solution having a composition suitable for use as the nanostructure solution in step a) of the method for radiolabeling a plurality of spherical nanostructures described above. The volume of the formulation is such that the resulting radiolabeled nanostructures are sufficient for quality control operations and at least one dose to a patient. Typically, the volume is less than 10 ml.
[0433] The kit further includes a volume of an aqueous solution of a pharma- ceutically acceptable buffer, the volume being contained in a suitable container, such as a rubber-capped pharmaceutical glass vial, and having a pH of at least 6. The buffer is of sufficient strength and volume and has a sufficiently high pH to be suitable for use in adjusting the pH in step c) of the method described above.
[0434] The kit further includes instructions for use to enable the implementation of the radiolabeling method. The instructions allow appropriately trained and / or certified personnel to carry out the method. The instructions preferably also detail the procedure for formulating the radiolabeled nanostructures into a dosage form to be administered to a patient. The instructions preferably also detail appropriate quality control measures. The instructions may also include instructions regarding handling and disposal of radioactive waste, administration of the resulting radiopharmaceutical to a patient, dosage calculation instructions, and imaging instructions.
[0435] The kit may further comprise a mixing vessel suitable for use in steps b) and c) of the above method. The vessel may be of a suitable size to contain the solution of radiolabeled nanostructures obtained at the end of the radiolabeling process, or may be much larger so as to allow dilution of the solution of radiolabeled nanostructures to a much larger volume. Such dilution may be advantageous when the radiolabeled nanostructures are to be administered by slow infusion.
[0436] The kit may further include equipment for sterile filtration, such as one or more syringe filters, a syringe, and a receiving vessel.
[0437] The kit may further comprise a pharma- ceutically acceptable diluent, such as saline (0.90% (w / v) NaCl in water) or a calcium-containing buffer.
[0438] The kit may further comprise a quality control device. Such a quality control device may comprise one or more centrifugal filters, allowing the determination of the activity of the permeate, thereby allowing the quantification of the binding of the radioisotope. Such a quality control device may also comprise the components required to carry out the chromatographic method, such as TLC plates (thin layer chromatography plates) suitable for controlling the type and radiochemical purity of the radiolabeled nanostructures, eluents, and sample preparation components for analysis by HPLC (high performance liquid chromatography).
[0439] The kit may further include equipment for shielding against ionizing radiation. Such equipment may include a shielded container suitable for storing and transporting containers for radioactive materials. Such a shielded container may be of a size and shape suitable for enclosing the containers that are part of the kit. Such equipment for shielding against ionizing radiation may also include shielded equipment for handling liquids, such as shielded syringes.
[0440] The kit may also include secondary and tertiary containers that allow the components of the kit to be assembled into one or a few units suitable for commercial storage and shipping of the kit. Such containers may include paper and / or plastic boxes and / or plastic or paper bags. Such containers may be suitable for freezer storage of the kit or portions of the kit.
[0441] The kit may also include one or more identifiers, such as one or more bar codes or one or more RFID (radio frequency identification) chips. Such identifiers may be present in or on the kit, or in one or more containers or containers contained in the kit. The identifiers may be used to uniquely identify the kit for quality control or inventory purposes.
[0442] The kit may contain all components necessary for the preparation of a pharmaceutical formulation of radiolabeled nanostructures suitable for injection into a patient, except for the radioisotope. It is also possible that the components necessary for the preparation of a pharmaceutical formulation of radiolabeled nanostructures typically found in a preparative radiopharmacy are not included in the kit. In that case, the instructions will detail the additional equipment required to achieve radiolabeling.
[0443] In one embodiment, the aqueous solution of spherical nanostructures included in the kit is a pharmaceutical composition according to the present disclosure. Thus, the aqueous solution of spherical nanostructures included in the kit may comprise a plurality of spherical nanostructures according to the present disclosure, water, and at least one excipient. The aqueous solution of spherical nanostructures included in the kit may further comprise 0.1-10 mg / ml thioglycerol, 0.03-3 mg / ml gentisic acid, and 3-300 mg / ml glycerol. Preferably, the pH of the composition is less than 3.5.
[0444] In another embodiment, the aqueous solution of spherical nanostructures included in the kit is a pharmaceutical composition according to the present disclosure and the aqueous solution of a pharma- ceutical acceptable buffer comprises Tris (tris(hydroxymethyl)aminomethane).
[0445] In a further embodiment, the kit further comprises equipment for quality control including equipment and reagents for sample preparation for analysis by size exclusion chromatography. EXAMPLES
[0446] Examples of different embodiments of the present disclosure are described below.
[0447] General Experimental Details Materials, reagents, and solvents were obtained commercially and used without further purification unless otherwise noted. Solvents were reagent grade or similar unless otherwise noted. Reactions were run under N2 unless otherwise noted.
[0448] SIR-200 resin, a thiolated polystyrene resin, was purchased from ResinTech, USA (resintech.com) and was used after activation with aqueous NaHCO3 solution, careful washing with ethanol and toluene, and azeotropic drying.
[0449] HPLC (High Performance Liquid Chromatography) was performed on a Hewlett Packard Series 1100 equipped with an Agilent Poroshell 120 EC-C18 4.6 x 50 mm column, a DAD detector (Diode Array Detector) recording at 220 nm, and an ELSD detector (Evaporative Light Scattering Detector) (ELSD settings: 40 °C, 1.4 L N2 / min, Gain = 4, Impactor on) using a nonlinear gradient starting from 43% (vol / vol) acetonitrile in water at 1 ml / min with an oven temperature of 40 °C.
[0450] DLS was measured using a Malvern Instruments Zetasizer Nano ZEN3600 and processed using the general process settings in the Zetasizer software.
[0451] SEC (size exclusion chromatography) was performed on a Younglin Instrument YL9100 equipped with an Agilent Bio SEC-5 1000 Å column eluting at 1.2 ml / min at ambient temperature, a DAD detector recording at 220 nm, 280 nm, and 560 nm, and an ELSD detector (ELSD settings: 60° C., 1.2 L N2 / min, gain=4).
[0452] NMR spectra were obtained using a Varian Unity Inova 400MHz ( 1 H is 399.95MHz, 13C is 125.68MHz) spectrometer. 1 H NMR and 13 C NMR was recorded using the residual solvent peak as the internal standard.
[0453] In the examples below, where purity is mentioned, this means chromatographic purity (area / area) from either HPLC-ELSD or SEC-ELSD chromatograms for molecular compounds and nanostructures, respectively.
[0454] 1,7-Bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane, 1-(ω-methyl-(ethyleneoxy) 45 The compounds, 3,5-bis(3-(triethoxysilyl)propyloxy)benzene and 2,2-diallyl-propane-1,3-diol, were synthesized according to literature procedures.
[0455] acronym Dichloromethane (DCM), ethyl acetate (EtOAc), tris(hydroxymethyl)aminomethane (Tris), m-PEG 45-OTs (m-PEG45-Tosylate), GF / A Filter (Glass Microfiber Filter, Grade GF / A), Polyethersulfone (PES), Revolutions Per Minute (RPM), Tangential Flow Filtration Filter (TFF Filter).
[0456] Example 1 - Synthesis of nanostructures Nanostructures according to the present disclosure were synthesized, filtered, and formulated as described below. This example illustrates the large-scale laboratory-scale synthesis of such nanostructures.
[0457] Example 1A – Synthesis of core nanostructure A 5 liter jacketed reactor was fitted with a mechanical stirrer, a temperature probe, and a reflux condenser with the top connected to a vacuum-nitrogen manifold. The reactor was charged with 93.60 g of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane with a purity of 94.5% and 4,501 g of 90.0% (volume / volume) aqueous ethylene glycol prepared by mixing 4,414.0 g of ethylene glycol with 440.5 g of ultrapure water. The solution was degassed. With stirring, the mantle temperature was increased to 155° C. over 30 minutes, during which the solution became clear. After 1.5 hours at the set mantle temperature, a gentle reflux was obtained and the mantle temperature was adjusted to 151° C. The reaction mixture was held at reflux for 47 hours and then cooled to 20° C. The nanostructure solution was filtered through a dual glass fiber filter (GF / A).
[0458] TIFF2025513684000017.tif12170
[0459] Example 1B - Adding an anchor layer A 5 liter jacketed reactor equipped with a mechanical stirrer, temperature probe, and connection to a vacuum-nitrogen manifold was charged with 4,338 g of the precursor nanostructure solution from Example 1A. The mantle temperature was set to 100° C., and when the internal temperature exceeded 99° C., 116.48 g of bis(triethoxysilyl)methane was added. The mixture was stirred at 300 RPM for 5 minutes, after which the mixture became homogeneous and the stirring speed was reduced to 150 RPM. Heating was continued for 4 hours, after which the solution was cooled to ambient temperature and filtered through a double glass fiber filter.
[0460] TIFF2025513684000018.tif7170
[0461] Example 1C - Adding a Coating Layer A 10 liter jacketed reactor equipped with a mechanical stirrer, temperature probe, dropping funnel heated to 40° C. with a heating fan, and a reflux condenser with the top connected to a vacuum-nitrogen manifold was charged with 6,330 g of 90% (vol / vol) aqueous ethylene glycol and 3,902 g of the solution of primed nanostructures from Example 1B. The jacket temperature was set at 125° C. for 1 hour and then reduced to 110° C. 548.2 g of 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45 A coating solution was prepared by dissolving 1,2-dichlorophenyl)heptane (prepared as described in Example 19) in 548.2 g of absolute ethanol with heating to 40° C. When the internal temperature of the reactor reached 105° C., 250 ml of coating solution was added. The remaining coating solution was added slowly through the dropping funnel at 50 ml / hr. The jacket temperature was held at 110° C. for 48 hours after starting the addition of the coating solution to the reactor, after which it was cooled to ambient temperature.
[0462] Example 1D – Filtration of coated nanostructures The crude reaction mixture was transferred to a 20 liter Nalgene jug. The reactor was rinsed with ultrapure water (5+4 liters) and the rinse was added to the reaction mixture. The solution was filtered through a filtration apparatus consisting of 1.2 μm, 0.45 μm, and 0.2 μm filters connected in series and the filter was washed with 3 liters of ultrapure water. The filtered solution was diluted with 5,400 cm until the ethylene glycol concentration was less than 500 ppm. 2 The mixture was purified by ultrafiltration using a 300 kD TFF filter and then concentrated to 1.3 liters.
[0463] TIFF2025513684000019.tif7170
[0464] Example 1E – Formulation of filtered coated nanostructures A mixture of 423 g of the coated nanostructure solution from Example 1D, 1.24 g of thioglycerol, 369 mg of gentisic acid, and 35.0 g of glycerol was diluted to 1,154 ml with ultrapure water to obtain a composition containing 0.1% (w / v) (1.1 mg / ml) thioglycerol, 0.03% (w / v) (0.32 mg / ml) gentisic acid, and 3% (w / v) (30 mg / ml) glycerol. The solution was filtered through a 0.2 μm polyethersulfone (PES) filter. The solution was divided into 5 ml vials, frozen, and stored at −70° C.
[0465] Example 1F - 175 Lu and Ca 2+ A filtered coated nanostructure formulation comprising: 1.41 g of thioglycerol and 425 mg of gentisic acid were added to 885 g of the solution of coated nanostructures from Example 1D. The solution was filtered through a 0.2 μm PES filter, after which 8.76 g of a 747 mM aqueous solution of LuCl3 was added, and the solution was heated in a water bath at 63.5° C. for 105 minutes. To this solution, 92.6 g of a 2 M Tris buffer with a pH of 8.9 was added. It was then heated in a water bath at 63.5° C. for 120 minutes and cooled in an ice bath. To this solution, 25.2 g of a 1,422 mM solution of CaCl2 and 38.7 g of glycerol were added at ambient temperature. It was then diluted with 243 g of water and filtered through a 0.2 μm PES filter. The solution was divided into 5 ml vials, frozen, and stored at −70° C.
[0466] Example 2 - Synthesis of nanostructures Nanostructures according to the present disclosure were synthesized, filtered, and formulated as described below. This example describes a method for producing nanomaterials on a small scale with average particle sizes approaching the lower limits of the present disclosure.
[0467] Example 2A – Synthesis of core nanostructure 6.06 g of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane of 96% purity, 248 ml of 80% (vol / vol) aqueous ethylene glycol, and 20.3 mg of rhodamine isothiocyanate in 1.74 ml of ethylene glycol were mixed in a 500 ml round bottom flask. The solution was degassed and divided into 19 vials. The vials were stoppered with septa and heated to 125° C. in an oil bath for 302 hours. The solutions from all the vials were pooled and filtered through glass fiber filters.
[0468] TIFF2025513684000020.tif7170
[0469] Example 2B - Adding an anchor layer A 10 ml sample of the precursor nanostructure solution from Example 2A was placed in a vial and heated to 100° C. in an oil bath. After 15 minutes, 315 mg of bis(triethoxysilyl)methane was added with vigorous stirring. Heating was maintained for 4 hours with gentler stirring.
[0470] TIFF2025513684000021.tif7170
[0471] Example 2C - Adding a Coating Layer A 1.75 ml sample of the solution of primed nanostructures from Example 2B was diluted to 5 ml with 80% (vol / vol) aqueous ethylene glycol in a two-neck round-bottom flask fitted with a reflux condenser at the vertical neck connected at its top to a vacuum-nitrogen manifold and the side neck plugged with a septum. This solution was heated in a preheated 110° C. oil bath for 10 minutes, followed by addition of 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45 60 μl of a 50% (weight / weight) solution of 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45 An additional 510 μl of the (-methyl)heptane solution was added via syringe pump at a rate of 27 μl / hr. After a total of 48 h, the solution was allowed to cool to ambient temperature.
[0472] Example 2D – Filtration of coated nanostructures The nanostructure solution from Example 2C was diluted to 25 ml with water and filtered through a 0.2 μm polyethersulfone (PES) syringe filter. The resulting solution was diluted to 800 ml with water and concentrated to approximately 20 ml using a tangential flow filtration device with a nominal cutoff of 300 kD. The dilution-concentration procedure was repeated a total of four times, after which the solution was further concentrated to 4.3 ml with a spin filter with a nominal cutoff of 300 kD.
[0473] TIFF2025513684000022.tif7170
[0474] Example 3 – Synthesis of nanostructures Nanostructures according to the present disclosure were synthesized, filtered, and formulated as described below. This example illustrates a method to produce nanostructures under pressure, which allows flexibility in solvent selection for the desired temperature.
[0475] Example 3A – Synthesis of core nanostructure A 250 mL bomb vial was charged with 11.35 g of 96% pure 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane and 175 mL of 80% (volume / volume) aqueous ethylene glycol. The solution was degassed and placed under a nitrogen atmosphere. The bomb vial was sealed and heated to 125° C. in an oil bath for 307 hours. The solution was filtered through a glass fiber filter.
[0476] TIFF2025513684000023.tif7170
[0477] Example 3B - Adding an anchor layer A 10 ml sample of the precursor nanostructure solution from Example 3A was placed in a vial and heated to 100° C. in an oil bath. After 20 minutes, 809 mg of bis(triethoxysilyl)methane was added with vigorous stirring. Heating was maintained for 4 hours with gentler stirring.
[0478] TIFF2025513684000024.tif6170
[0479] Example 3C - Adding a Coating Layer A 1.025 ml sample of the solution of primed nanostructures from Example 3B was diluted to 7.5 ml with 80% (vol / vol) aqueous ethylene glycol in a two-neck round-bottom flask fitted with a reflux condenser at the vertical neck connected at its top to a vacuum-nitrogen manifold and the side neck plugged with a septum. This solution was heated in a preheated 110° C. oil bath for 10 minutes and then diluted with 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45200 μl of a 50% (weight / weight) solution of 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45 An additional 805 μl of the (-methyl)heptane solution was added via syringe pump at a rate of 43 μl / hr. After a total of 48 h, the solution was allowed to cool to ambient temperature.
[0480] 3D - Filtration of coated nanostructures The nanostructure solutions from two identical batches were combined, diluted to 50 ml with water, and filtered through a 0.2 μm polyethersulfone (PES) syringe filter. The resulting solution was diluted to 800 ml with water and concentrated to approximately 20 ml using a tangential flow filtration device with a nominal cutoff of 300 kD. The dilution-concentration procedure was repeated a total of five times, after which the solution was further concentrated to 11.3 ml with a spin filter with a nominal cutoff of 300 kD.
[0481] TIFF2025513684000025.tif7170
[0482] Example 4 – Synthesis of core nanostructures with different particle sizes Solutions of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane in 80% (vol / vol) aqueous ethylene glycol were prepared by dilution from a stock solution at concentrations of 34, 37, 41, 45, 50, 55, 61, 67, 75, and 82 mM. 10 ml samples of each solution were placed in reaction vials and heated to 125 °C in an oil bath for 402 h. The diameters of the resulting nanostructures were 13.5, 14.3, 15.4, 15.3, 16.1, 17.4, 17.7, 20.5, 22.6, and 23.9 nm, respectively.
[0483] Example 5 – Synthesis of primed core nanostructures with anchor layers of different thicknesses Core nanostructures synthesized according to Example 2A were treated with 2.5, 3, 5, and 7 molar equivalents of bis(triethoxysilyl)methane relative to the 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane used to synthesize the core nanostructures in a procedure similar to that used in Example 2B. The resulting primed nanostructures had anchor layers with thicknesses of 0.5, 0.6, 0.75, and 0.95 nm.
[0484] Example 6 – Synthesis of nanostructures with different coatings Example 6A - 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 67 Synthesis of (-methyl)heptane-coated nanostructures 1,7-Bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 67 -methyl)heptane, 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45 -methyl)heptane was synthesized in the same manner.
[0485] A 13.4 ml sample of the solution of primed nanostructures from Example 1B was diluted to 36.1 ml with 90% (vol / vol) aqueous ethylene glycol in a two-neck round-bottom flask fitted with a reflux condenser at the vertical neck connected at its top to a vacuum-nitrogen manifold and the side neck plugged with a septum. This solution was heated in a preheated 110° C. oil bath for 20 minutes and then diluted with 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 67 1,500 μl of a 50% (weight / weight) solution of 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 67 An additional 5,200 μl of the (-methyl)heptane solution was added via syringe pump at a rate of 266 μl / hr. After a total of 48 hours, the solution was allowed to cool to ambient temperature.
[0486] The resulting nanostructure solution was diluted to 150 ml with water and filtered through a dual glass fiber filter followed by a 0.2 μm polyethersulfone (PES) syringe filter. The resulting solution was diluted to 800 ml with water and concentrated to approximately 20 ml using a tangential flow filtration device with a nominal cutoff of 70 kD. The dilution-concentration procedure was repeated a total of four times, after which the solution was further concentrated to 20 ml with a spin filter with a nominal cutoff of 300 kD.
[0487] Nanostructures synthesized in this manner do not aggregate even when exposed to 20 mM CaCl2.
[0488] TIFF2025513684000026.tif7170
[0489] Example 6B - 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 91 Synthesis of (-methyl)heptane-coated nanostructures 1,7-Bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 91 -methyl)heptane, 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45 -methyl)heptane was synthesized in the same manner.
[0490] A 4.1 ml sample of the solution of primed nanostructures from Example 1B was diluted to 11 ml with 90% (vol / vol) aqueous ethylene glycol in a two-neck round-bottom flask fitted with a reflux condenser at the vertical neck connected at its top to a vacuum-nitrogen manifold and the side neck plugged with a septum. This solution was heated in a preheated 110° C. oil bath for 15 minutes and then diluted with 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 91 530 μl of a 50% (weight / weight) solution of 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 91An additional 2,120 μl of the (-methyl)heptane solution was added via syringe pump at a rate of 109 μl / hr. After a total of 48 hours, the solution was allowed to cool to ambient temperature.
[0491] The resulting nanostructure solution was diluted to 40 ml with water and filtered through a dual glass fiber filter followed by a 0.2 μm polyethersulfone (PES) syringe filter. The resulting solution was diluted to 800 ml with water and concentrated to approximately 20 ml using a tangential flow filtration device with a nominal cutoff of 70 kD. The dilution-concentration procedure was repeated a total of four times, after which the solution was further concentrated to 10 ml with a spin filter with a nominal cutoff of 300 kD.
[0492] Nanostructures synthesized in this manner do not aggregate even when exposed to 20 mM CaCl2.
[0493] TIFF2025513684000027.tif7170
[0494] Example 7 – Determination of elemental composition of nanostructures and average bond number per monomer The low molecular weight components of the nanostructure sample from Example 1E were removed by 10 cycles of spin filtration-concentration by dilution using a spin filter with a 10 kDa cutoff. [P] and [Si] were determined by ICP-OES. The entire sample was lyophilized to constant weight and analyzed for [C], [P], and [H] by combustion analysis. TIFF2025513684000028.tif47170
[0495] Ingredient C7H 12 P2Si2O9, CH2Si2O3, C 190 H 373 SiO 91 , H2O, and C2H4O2 mole fractions fitted to the experimental elemental composition. 12 P2Si2O9, CH2Si2O3, and C 190 H 373 SiO 91are 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane, bis(triethoxysilyl)methane, and 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45 represents a theoretical monomer residue with six bonds to the polymer, derived from (-methyl)heptane. Each H2O represents two dangling silanol bonds, i.e., the formal hydrolysis of a Si-O-Si group in the polymer structure to two Si-OH groups. C2H4O2 represents ethylene glycol bound to the siloxane network.
[0496] From fitting, C7H 12 P2Si2O9 is 1, CH2Si2O3 is 2.49, C 190 H 373 SiO 91 The relative compositions obtained were 0.101 for H2O, 3.36 for H2O, and 0.14 for C2H4O2, indicating an average of 4.1 bonds to the rest of the polymer network per monomer residue, i.e., 68% of the theoretical maximum of 6 bonds per monomer residue.
[0497] Example 8 - NMR of nanostructures A sample of core nanostructures similar to that from Example 1A, and a sample of primed nanostructures similar to the product from Example 1B were transferred to DO by first exchanging the solvent into water using repeated dilution-concentration cycles on a spin filter with a nominal cutoff of 100 kD, and then exchanging the water into DO in the same manner. A sample of coated nanostructures according to Example 1D was also transferred to DO by repeated dilution-concentration cycles on the spin filter in a similar manner.
[0498] Core nanostructure and primer-treated core nanostructure 1The H-NMR spectra are shown in Figure 3. The top spectrum is that of the core nanostructure, which has been shifted from that of the primed nanostructure for clarity. The inset is a zoomed-in version of the same spectrum, showing prominent features in the region around 0 ppm.
[0499] The main peak of the core nanostructure is extremely broad, peaking at approximately 25 ppm (12,500 Hz) due to the high degree of crosslinking of the core nanostructure. The spectrum of the primed nanostructure shows essentially the same features, except for a smaller but similarly broad peak centered at 0.25 ppm, which corresponds to the methylene moiety of the anchor layer. This demonstrates the high degree of crosslinking of the anchor layer.
[0500] Core Nanostructure 31 The P-NMR spectrum is shown in Figure 4. A single peak is seen centered around 25 ppm. The presence of only one phosphorus chemical environment indicates complete hydrolysis of the phosphonate ester.
[0501] Coated nanostructures 1 The H-NMR spectrum is shown in Figure 5. The spectrum is completely dominated by the PEG CH2 signal, which is very sharp and indicates considerable mobility of the PEG chain, consistent with a single point of attachment to the surface.
[0502] Example 9 - Comparison of nanostructure loading by the disclosed method with conventional loading Samples of the nanostructures according to Example 1E were loaded with LuCl3 by the method of the present disclosure (low pH) and the reference method (neutral pH), and the binding strength of Lu was evaluated by competitive binding with the reference chelator EDTA.
[0503] In the low pH loading procedure (method of the present disclosure), a 1,000 μl sample of the nanostructure solution at pH 2.3 was mixed with 115 μl of a 21 mM solution of LuCl3 and incubated for 1 hour at 60° C. The pH was then adjusted by adding 145 μl of 2 M Tris buffer at pH 8, followed by an additional incubation at 60° C. for 2 hours.
[0504] In the neutral pH loading procedure (Reference Method), a 1,000 μl sample of the nanostructure solution was adjusted to pH 7.4 by the addition of 130 μl of 2 M Tris buffer, pH 8. The buffered nanostructure solution was then mixed with 115 μl of a 21 mM solution of LuCl3 and incubated at 60° C. for 1 hour.
[0505] The LuCl3-loaded nanostructure solutions were diluted to 0.2 mM Lu in 50 mM Tris buffer, treated with EDTA (10 equivalents relative to Lu), and incubated at 37°C for 1 h. After incubation, an aliquot of each sample was set aside for determination of [Lu] by ICP-OES without filtration, and a separate aliquot of each sample was filtered through a 3 kDa spin filter for determination of [Lu] not bound to the nanostructures by ICP-OES of the permeate. The relative amount of Lu not bound to the nanostructures was determined as [Lu] permeate / [Lu] unfiltered The nanostructures loaded by the method of the present disclosure were able to extract 6.6% of the loaded lutetium with EDTA, whereas the reference method was able to extract 17.1% of the loaded lutetium, which is more than 2.5 times the amount. The percentages are the average of two independent experiments.
[0506] This demonstrates the stronger metal chelating ability of the nanostructures loaded with metal ions by the method of the present disclosure.
[0507] Example 10 - Loading of cold equivalents of radionuclides on nanostructures Samples of nanostructures from Example 1E were loaded with SmCl3, YCl3, GdCl3, EuCl3, TbCl3, ZrCl4, HoCl3, PrCl3, and Ga(NO3)3, respectively, by treating a 1 ml sample of the nanostructure solution with 2.4 μmol of the respective salt in water, incubating the resulting mixture for 1 h at 60° C., adjusting the pH to about 7.2 with 2 M Tris buffer, and incubating the resulting mixture for 2 h at 60° C. [P] and [M] were determined for each sample by ICP-OES, an aliquot of each sample was filtered through a 3 kDa spin filter, and the amount of metal not bound to the nanostructures was measured as [M] in the permeate. TIFF2025513684000029.tif103170
[0508] From Table 2 it is clear that the cold equivalents of all radionuclides tested bind strongly to the nanostructures.
[0509] Example 11 - Comparison of metal bond stability with and without sodium metabisulfite A sample of the nanostructures according to Example 1D was loaded with excipients prior to loading with LuCl3, and the Lu binding strength of the nanostructures was evaluated by competitive binding with the reference chelator EDTA.
[0510] Five samples of nanostructures according to Example 1D, containing no additive, 3.3% (wt / vol) glycerol, 3.3% (wt / vol) sodium metabisulfite, 0.3% (wt / vol) thioglycerol, and 0.03% (wt / vol) gentisic acid, respectively, were loaded with Lu in the form of LuCl3, with a Lu to P ratio of 25:1. The samples were diluted to 0.2 mM Lu in 50 mM Tris buffer, treated with EDTA (10 equivalents relative to Lu), and then incubated at 37°C for 48 hours. After incubation, an aliquot of each sample was set aside for determination of [Lu] by ICP-OES without filtration, and a separate aliquot of each sample was filtered through a 3 kDa spin filter for determination of [Lu] not bound to the nanostructures by ICP-OES of the permeate. The relative amount of Lu not bound to the nanostructures was determined as [Lu] permeate / [Lu] unfiltered The percentage of loaded lutetium that could be extracted with EDTA was essentially the same as that from the sample without additive, with 16% for all samples with additive and 17% for the sample without additive. However, in the sample treated with sodium metabisulfite, 39% of the loaded Lu could be extracted from the nanostructures by EDTA. This clearly shows the advantage of using thioglycerol and / or gentisic acid as antioxidants for the nanostructures of the present disclosure over sodium metabisulfite.
[0511] Example 12 – In a tumor-bearing mouse model 175 Biodistribution experiment of Lu-loaded nanostructures Representative Preparation of Test Article: Test Article C A 4 ml sample of the nanostructure solution from Example 4D (112 μmol P) was treated with 228 μl of a 19.7 mM LuCl3 solution (4.5 μmol Lu) and heated to 60° C. for 1 h, after which 1.269 ml of 1 M Tris buffer (pH 7.47) was added. After an additional 2 h at 60° C., the solution was filtered through a 0.2 μm PES syringe filter.
[0512] A 3.47 ml sample of the resulting nanostructure solution was mixed with 3.80 ml saline and 140 μl of 99 mM CaCl2 solution, after which the pH was adjusted to 7.2 with 12 μl of 1 M NaOH solution. The solution was diluted to a total volume of 7.5 ml with saline and then filtered through a 0.2 μm PES syringe filter.
[0513] Average diameter (DLS)=36.0nm, [P](ICP-OES)=9.9mM, [Si](ICP-OES)=46mM, [Lu](ICP-OES)=0.39mM
[0514] Test samples A and B Test specimens A and B were similarly prepared starting from nanostructure solutions according to Examples 2D and 1D, respectively. Test item A: Average diameter (DLS)=21.3nm, [P](ICP-OES)=8.9mM, [Si](ICP-OES)=48mM, [Lu](ICP-OES)=0.39mM Test sample B: average diameter (DLS) = 27.7 nm, [P] (ICP-OES) = 8.7 mM, [Si] (ICP-OES) = 41 mM, [Lu] (ICP-OES) = 0.39 mM
[0515] Biodistribution The tissue distribution of the test article was investigated after intravenous injection into a tumor-bearing mouse model. The injectable test article was analyzed for lutetium and silicon content by ICP-OES. The lutetium value obtained represents the total amount of lutetium injected (i.e., 100%).
[0516] Female BALB / c mice received 4T1 cells (1 × 10 5 Tumors were induced by inoculating mice with 100% ethanol (100% ethanol) cells. Eighteen days after inoculation, the tumor volume was 200–300 mm. 3 The mice were then divided into groups.
[0517] Each test article was administered intravenously at 2 μmol Lu / kg and 5 ml / kg. Animals were divided into 4 groups per test article (n=5 mice / group) and groups were sacrificed at 6, 24, 48, and 168 hours after injection. Three animals served as controls and were not dosed.
[0518] At the end of the experimental period, blood samples were taken and plasma was prepared by removing blood cells. After termination, organs were removed (liver, tumor, and thigh muscle). Plasma and digested tissue samples were analyzed for lutetium content by ICP-OES and are shown in Table 3. TIFF2025513684000030.tif114170
[0519] As can be seen from Table 3, the coated nanostructures according to the present disclosure have long circulation, i.e., long plasma half-lives. The plasma half-lives calculated based on the plasma Lu concentration were 23.9 hours for test article A, 23.1 hours for test article B, and 19.8 hours for test article C. In addition, a significant proportion of the nanostructures can be seen to be distributed in the tumor. This demonstrates that the nanostructures according to the present disclosure are suitable for use in pharmaceutical compositions and in cancer imaging and / or therapy.
[0520] Example 13 – For the treatment of cancer in tumor-bearing mouse models 177 Use of Lu-loaded nanostructures Ten-week-old female BALB / c mice were injected with 4T1 cells (1 × 10 5 Tumors were induced by inoculation of mice with 100% ethanolamine (100% ethanolamine) and 100% ethanolamine (100% ethanolamine) ....
[0521] The nanostructure according to Example 1D is treated with the nanostructure solution 177 By treating with a solution of LuCl3 and then adjusting the pH with Tris buffer, approximately one atom of 177 Up to the concentration of Lu 177 Lu was loaded and formulated for injection by adding CaCl2 and saline.
[0522] Tumor volume is 200-300 mm on the 14th or 15th day after inoculation. 3 At that point, the treatment group (n=16) 177 Lu-loaded nanostructures were injected at a dose of 218 MBq / kg, and the control group (n=10) received saline. Antitumor efficacy was monitored by following tumor growth and overall survival.
[0523] The treatment group showed a significant increase in mean and median survival times compared to the control group. Tumor growth was significantly delayed in the treatment group. See Figure 7. TIFF2025513684000031.tif42170
[0524] This demonstrates the use of nanostructures according to the present disclosure as intermediates in the manufacture of pharmaceutical compositions, the use of nanostructures according to the present disclosure as intermediates in the manufacture of pharmaceutical compositions for use in the treatment of cancer, and the use of nanostructures according to the present disclosure as intermediates in the manufacture of carriers for radionuclides.
[0525] Example 14 – In healthy female and male Sprague-Dawley rats 177 Pharmacokinetics of Lu-loaded nanostructures after intravenous administration The nanostructures according to Example 1E were treated with the nanostructure solution. 177 By treating with a solution of LuCl3 and then adjusting the pH with Tris buffer, approximately one atom of 177 Up to the concentration of Lu 177 Lu was loaded and formulated for injection by adding CaCl2 and saline.
[0526] Healthy female and male Sprague-Dawley rats were administered 8MBq / kg 177 Lu radiolabeled nanostructures were injected intravenously. 177 Lu was assessed from individual rats at 1, 6, 24, 72, 168, 504, and 840 hours post-injection (n=5 per time point and sex) by an automated gamma counter.
[0527] Plasma half-life (t 1 / 2 ) was calculated by fitting an exponential function to the decay-adjusted activity. 1 / 2 (female) = 31.1 hours. t 1 / 2 (Male)=28.5 hours.
[0528] This demonstrates the long circulation of the nanostructures and the use of the nanostructures according to the present disclosure as intermediates in the manufacture of pharmaceutical compositions, and the use of the nanostructures according to the present disclosure as intermediates in the manufacture of carriers for radionuclides.
[0529] Example 15 – Concentration of nanostructure solutions demonstrating high solubility of nanostructures in water A 20 ml sample of the nanostructures from Example 1D was concentrated on a 300 kDa spin filter. The concentration of P was measured to be 328 mM by ICP-OES, corresponding to approximately 25% (weight / volume) nanostructures in solution. The hydrodynamic diameter was measured to be 27.4 nm, and no aggregates were visible upon visual inspection, indicating the absence of aggregation.
[0530] This demonstrates the high solubility and resistance to aggregation of the nanostructures according to the present disclosure.
[0531] Example 16 – In healthy mice 175 Pharmacokinetics of Lu-loaded nanostructures The nanostructures according to Example 1D were subjected to the same method as in Example 1F. 175 Lu was carried.
[0532] Female healthy BALB / c AnN mice were injected with the nanostructures at a dose of 2 μmol Lu / kg. Blood was collected at 1, 6, and 24 hours (group 1, 5 animals) and at 24, 48, and 96 hours (group 2, 5 animals) for determination of [Si] and [Lu]. Plasma [Si] and [Lu] were determined by ICP-OES. For group 1, the percentage of Si and Lu remaining in plasma at each time point was normalized to the level at 1 hour, and for group 2, the percentage of Si and Lu remaining in plasma at each time point was normalized to the level at 24 hours. The normalized data are shown in Table 5. TIFF2025513684000032.tif59170
[0533] From Table 5, it can be seen that the pharmacokinetics of Lu and Si are identical within the experimental uncertainty. The codistribution of Lu and Si strongly indicates that Lu remains bound to the nanostructures for the duration of the experiment.
[0534] Example 17 – Accelerated ageing of nanostructures with and without excipients Nanostructures with (formulated as in Example 1E) and without (diluted to 60 mM P in water as in Example 1D) excipients were divided into 1 ml vials and incubated at 60° C. for accelerated aging. Samples were removed after 7, 14, and 34 days for analysis by SEC-ELSD. Samples subjected to accelerated aging showed increased amounts of molecular impurities attributed as polyethylene glycol, including degradation products of the coating layer of the nanostructures. None of the samples showed signs of aggregation. The retention time (tr) of the peak corresponding to the nanostructures remained unchanged (Δtr / tr<0.005, below the detection limit of the method used) for samples formulated as in Example 1E, i.e., with excipients, and increased slightly for samples without excipients (formulated as in Example 1D), indicating a slight decrease in nanostructure particle size (Δtr / tr of about 0.02), indicating degradation of the nanostructures. TIFF2025513684000033.tif72170
[0535] It is evident from Table 6 that the degradation of the nanostructures is greatly reduced in the samples formulated according to the present disclosure.
[0536] Example 18 - Storage of samples of nanostructures formulated according to the present disclosure in a frozen state Samples of nanostructures from Example 1D were treated with either 3% (wt / vol) glycerol or 5% sucrose (wt / vol) and divided into vials. The vials were frozen in a -20°C freezer, stored in the freezer for 14 days, and allowed to thaw at room temperature. The samples were analyzed by SEC-ELSD for changes in the particle size profile of the nanostructures. The results are summarized in Table 7. TIFF2025513684000034.tif38170
[0537] Samples treated with glycerol did not show any change in particle size profile after freezing and storage at -70°C or after freezing at -70°C and storage at -20°C, whereas samples containing sucrose showed signs of aggregation of the nanostructures.
[0538] Example 19 - 1,7-Bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45 Synthesis of (Methyl)heptane Example 19A: 4,4-bis(ω-methyl-(ethyleneoxy) 45 Synthesis of (Methyl)hepta-1,6-diene Diallylpropanediol (22 g, 0.1411 mol) was dissolved in anhydrous toluene (2.61 L) and cooled in an ice bath. When the internal temperature was below 10° C., NaH (23.7 g, 0.593 mol, 60% (wt / vol) in mineral oil, 4.2 eq) was added in three portions while maintaining the temperature below 10° C. The slurry was then stirred at room temperature for 60 min, followed by m-PEG in anhydrous toluene (2.61 L). 45To an azeotropically dried solution of -OTs (1.071 kg, 0.9877 mmol, 3.5 equiv) was added at 0°C under N2. The reaction mixture was heated to reflux overnight and stirred under N2. The reaction was monitored by HPLC and upon completion, the temperature was reduced to 15°C and the reaction was quenched by dropwise addition of H2O (70 ml). The pH of the crude reaction mixture was adjusted to 5-7 with 1.0 M HCl (100 ml). The crude reaction mixture was divided into two equal portions for practical reasons and the two portions were extracted separately. Each half of the crude mixture was diluted with H2O (7.14 L). The temperature was increased to 60°C and NaCl (540 g) was added. The mixture was then stirred for 45 min and extracted three times with EtOAc (2.1 L). To the remaining aqueous phase, NaCl (200 g) was added and the mixture was extracted again three times with EtOAc (2.1 L). The last three extracted fractions had acceptable product purity (analyzed by HPLC) and were dried over MgSO4, filtered through dual GF / A filters, and the solvent was evaporated. The resulting residues were pooled, dissolved in H2O (2.0 L), and the pH was adjusted to pH 8 with 0.8 M aqueous NaHCO3 (100 ml). The aqueous phase was extracted three times with DCM (500 mL). The organic phase was dried over MgSO4, filtered, and evaporated to give a white residue.
[0539] Therefore, the extraction process was repeated for the other half of the crude mixture, and the final products of both extractions were pooled together with the products of another similarly sized batch synthesized in the same manner to obtain 4,4-bis(ω-methyl-(ethyleneoxy) 45 -methyl)hepta-1,6-diene (758 g, yield 66.36%, purity 96.8% (HPLC-ELSD)).
[0540] 1 H NMR(400MHz,CDCl3)δ5.80(m,2H),5.03(m,4H),3.70-3.60(s,540H),3.37(s,6H),3.22(s,4H),2.04(d,4H)
[0541] Example 19B - 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45Synthesis of (Methyl)heptane 4,4-bis(ω-methyl-(ethyleneoxy)) from Example 19A in toluene (5.5 L) 45 To an azeotropically dried solution of 1,2-dimethyl-2,4-hexanedione (714 g, 0.172 mol) was added triethoxysilane (1,117 g, 6.88 mol, 40 equiv.) under nitrogen at 22° C. Karstedt's catalyst (25.34 ml, 2% w / w in xylene, 1.14 mmol, 0.0066 equiv.) was added in 1 ml portions via syringe over 30 min resulting in an exotherm of ≦2° C. The reaction mixture was stirred overnight at 22° C. under nitrogen.
[0542] The reaction is analyzed for the disappearance of an olefinic proton. 1 The reaction mixture was monitored by H-NMR. The solvent was then evaporated and excess silane was removed by co-evaporation with anhydrous toluene (2.5 L) for a total of four times. The residue was redissolved in toluene (4.2 L), degassed with three vacuum / nitrogen cycles, and stirred with activated SIR-200 resin (175 g) at 60 °C for 3 days. The solution was filtered from the resin and the resin was washed with toluene (3 x 2.8 L). The collected fractions were filtered through a double GF / A filter, pooled, and the solvent was evaporated to give 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45 The resulting mixture was concentrated to give 1,3-dichlorophenyl)-1,3-dimethylphenylheptane as a white solid in quantitative yield (783.2 g, ≧99%, purity 94.4% (HPLC-ELSD)).
[0543] 1 H NMR(400MHz,C6D6)δ3.71(q,12H),3.70-3.40(s,400H),3.52(s,4H),3.35(s,6H),1.68(m,4H),1.59(m,4H),1.23(t,18H),0.79(t,4H)
[0544] Example 20 - Coating Monomer 1-(ω-methyl-(ethyleneoxy) 45 Reference nanostructures coated with (methyl)-3,5-bis(3-(triethoxysilyl)propyloxy)benzene (reference examples outside the scope of this disclosure) An 8 mL sample of solution of primed nanostructures with a hydrodynamic diameter of 15.1 nm and a phosphorus concentration of 99 mM, prepared as in Example 1B, was placed in a two-neck round-bottom flask fitted with a reflux condenser at the vertical end connected at the top to a vacuum-nitrogen manifold and the side end plugged with a septum. The solution was heated in a preheated 110° C. oil bath for 5 minutes, followed by addition of 1-(ω-methyl-(ethyleneoxy) 45 300 μl of a 50% (weight / weight) solution of 1-(ω-methyl-(ethyleneoxy) 45 An additional 1,970 μl of the (3-(triethoxysilyl)propyloxy)-3,5-bis(3-methyl)-3,5-bis(3-(triethoxysilyl)propyloxy)benzene solution was added via syringe pump at a rate of 99 μl / hr. After a total of 48 hours, the solution was allowed to cool to ambient temperature.
[0545] The resulting nanostructure solution was filtered through a 0.2 μm PES filter, diluted with water, and then diluted with 115 cm 2 The mixture was purified by ultrafiltration using a 300 kD TFF filter.
[0546] Nanostructures synthesized in this manner do not aggregate even when exposed to 20 mM CaCl2.
[0547] TIFF2025513684000035.tif7170
[0548] Example 21 - Comparison of in vivo circulation time between nanostructures according to the present disclosure and reference nanostructures Nanostructures similar to those in Example 1D (Test A) and reference nanostructures from Example 20 (Test B) were loaded with yttrium in the form of YCl3, with [P] / [Y] of 23 (±1). The test articles were formulated for injection by adjusting [Ca], pH, and osmolality to physiological levels with CaCl2, NaOH, and mannitol, respectively. The in vivo behavior of the test articles was investigated by injecting them into female BALB / c mice at a dose of 2 μmol Y / kg. Blood was collected 1, 6, and 24 hours after injection, and plasma was analyzed for [Y] and [Si] by ICP-OES. The results as circulating half-lives are shown in Table 8. TIFF2025513684000036.tif35170
[0549] As can be seen from Table 8, nanostructures according to the present disclosure exhibit significantly increased circulation times compared to reference nanostructures not within the scope of the present disclosure.
[0550] Example 22 - Further reference nanostructures (references outside the scope of this disclosure) Example 22A. Synthesis of Core Nanostructures According to Example 1c of WO 2015 / 144891 A1 The core nanostructure was synthesized according to Example 1c of WO 2015 / 144891 A1. A 150 ml pressure vial was charged with 3.896 g of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane and 65 ml of ethylene glycol was added. The clear solution was stirred briefly, and then 16 ml of water was added. The cloudy solution was degassed by repeated vacuum-nitrogen cycles, after which the pressure vial was sealed and heated to 120° C. for 33 hours.
[0551] TIFF2025513684000037.tif7170
[0552] Example 22B. Synthesis of nanostructures coated with [methoxy(polyethyleneoxy)propyl]trimethoxysilane (12 ethylene glycol units) without an anchor layer according to Example 2b of WO 2015 / 144891 A1 The nanostructures according to Example 22A were coated according to Example 2b of WO 2015 / 144891 A1. After 20 ml of the solution of the nanostructures from Example 23A was degassed by repeated vacuum-nitrogen cycles, the solution was heated in a preheated oil bath at 114° C. for 15 minutes. [Methoxy(polyethyleneoxy)propyl]trimethoxysilane (90%, 12 ethylene glycol units, 1,107 mg) was dissolved in 1.225 ml of ethylene glycol. 1.55 ml of the coating solution was added to the nanostructures at 150 μl / min. After 6 hours of heating, the solution was cooled, diluted with water to 100 ml, and filtered through a double GF / A glass fiber filter and a 0.2 μm PES syringe filter. The resulting solution was diluted with water to 800 ml and concentrated to approximately 20 ml using a tangential flow filtration device with a nominal cutoff of 300 kD. The dilution-concentration procedure was repeated a total of three times, after which the solution was further concentrated to 20 ml on a spin filter with a nominal cutoff of 300 kD.
[0553] TIFF2025513684000038.tif7170
[0554] Example 23 - Further hydrolytic stability comparison The coated nanostructures according to Example 1D (nanostructures according to the present disclosure) and Example 22B (reference example) were evaluated in an accelerated aging test.
[0555] A 500 μl aliquot of each nanostructure solution in a 1.5 ml crimp-cap vial was heated in an oven at 60° C. for 3 days and evaluated by SEC-ELSD. The relative amount of degradation products was determined as the sum of all peaks eluting after the peak corresponding to the nanostructure. TIFF2025513684000039.tif51170
[0556] As can be seen from Table 9, the coated nanostructures according to the present disclosure, i.e., Example 1D, produce significantly fewer molecular degradation products than the coated nanostructures according to WO 2015 / 144891, i.e., Example 22B, demonstrating that products containing nanostructures according to the present disclosure have a significantly longer shelf life.
[0557] Example 24 - Addition of a coating layer to unprimed nanostructures (example outside the scope of this disclosure) A two-necked round-bottom flask fitted with a reflux condenser at the vertical neck connected at the top to a vacuum-nitrogen manifold and with a septum-stopped side neck was charged with 5 ml of a solution of unprimed precursor nanostructures with an average diameter of 19.1 nm and a phosphorus concentration of 130 mM, formed by heating 5.74 g of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane in 105 ml of ethylene glycol and 26 ml of water at 125° C. for 285 hours. The nanostructure solution was degassed and lowered into a preheated 110° C. oil bath. After 5 minutes, 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45 400 μl of a 50% (weight / weight) solution of 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45 An additional 2.7 ml of the 3-methyl)heptane solution was added via syringe pump at a rate of 142 μl / hr. After a total of 48 hours, the solution was allowed to cool to ambient temperature. The solution was diluted to 25 ml with water and filtered through a 0.2 μm PES syringe filter. The resulting solution was diluted to 800 ml with water and concentrated to approximately 20 ml using a tangential flow filtration device with a nominal cutoff of 300 kD. The dilution-concentration procedure was repeated a total of three times, after which the solution was further concentrated to 6 ml with a spin filter with a nominal cutoff of 300 kD.
[0558] Average diameter (DLS)=29.0nm, [P](ICP-OES)=80mM, [Si](ICP-OES)=107mM
[0559] Nanostructures prepared in this manner precipitate when exposed to a physiologically relevant solution of 2 mM CaCl2.
[0560] In contrast, nanostructures according to the present disclosure are indefinitely stable with respect to aggregation under such conditions, see Example 1F where the nanostructures are formulated with greater than 25 mM CaCl 2 .
[0561] This demonstrates the reduced suspension stability of coated nanostructures without an anchor layer compared to coated nanostructures including an anchor layer according to the present disclosure.
[0562] Example 25 - Hydrodynamic size distribution of some nanostructure samples. TIFF2025513684000040.tif5170, and comparison with polydispersity index (PDI) Nanostructure samples with different dispersions were analyzed by DLS, and the dispersion of each sample was TIFF2025513684000041.tif6170 and the polydispersity index (PDI) was calculated (shown in Table 10). TIFF2025513684000042.tif100170
[0563] From Table 10, It can be seen that TIFF2025513684000043.tif6170 and PDI are correlated, and that both parameters represent the breadth of the size distribution of the nanostructure population. However, a simple, monotonic conversion between the two does not allow a good fit to the data. It can be concluded that TIFF2025513684000044.tif5170 and PDI capture different aspects of the shape of the particle size distribution.
Claims
1. A plurality of spherical nanostructures having an average hydrodynamic diameter of 20-50 nm, each nanostructure comprising: A central moiety comprising a monomer residue according to formula (I), During the ceremony, - Each R 1 , R 2 , R 3 , R 4 , R 5 , and R 6 is independently selected from the group consisting of H, a negative charge, and a covalent bond; - Each R 7 , R 8 , R 9 , and R 10 is independently selected from the group consisting of H, a negative charge, and a lower alkyl; 7 , R 8 , R 9 , and R 10 At least 95% of all of the groups are H or negatively charged; n is an integer from 2 to 5, m is an integer from 2 to 5, The central part and an anchor layer surrounding the central portion, the anchor layer comprising monomer residues according to formula (II): During the ceremony, - Each R 11 , R 12 , R 13 , R 14 , R 15 , and R 16 is independently selected from the group consisting of H, a negative charge, and a covalent bond; p is 1 or 2, An anchor layer; a coating layer surrounding the anchor layer, the coating layer comprising a monomer residue according to formula (III): During the ceremony, - Each R 17 , R 18 , R 19 , R 20 , R 21 , and R 22 is independently selected from the group consisting of H, a negative charge, and a covalent bond; q is an integer from 2 to 5, r is an integer from 2 to 5, - Each R 23 and R 24 is independently selected from the group consisting of H and lower alkyl; - s is an integer from 30 to 105, t is an integer from 30 to 105, A coating layer; A plurality of spherical nanostructures, the polymer nanostructures comprising:
2. X, which indicates the ratio of the number of monomer residues in the central portion to the total number of monomer residues in the nanostructure, CP is 5% to 58%, X, which indicates the ratio of the number of monomer residues of the anchor layer to the total number of monomer residues of the nanostructure AL is 39% to 93%, X represents the ratio of the number of monomer residues of the coating layer to the total number of monomer residues of the nanostructure. CL is between 0.75% and 4.5%, and 70% < (X CP +X AL +X CL 2. The plurality of spherical nanostructures of claim 1, wherein:
3. 3. The plurality of spherical nanostructures according to claim 1 or 2, wherein monomer residues according to formula (I) constitute at least 70% of the monomer residues of the central portion, and / or monomer residues according to formula (II) constitute at least 70% of the monomer residues of the anchor layer, and / or monomer residues according to formula (III) constitute at least 70% of the monomer residues of the coating layer.
4. the average hydrodynamic diameter is 22 to 37 nm; n=3, m=3, p=1, q=3 r=3, R 23 and R 24 is independently selected from the group consisting of lower alkyl; and / or X, which indicates the ratio of the number of monomer residues in the central portion to the total number of monomer residues in the nanostructure, CP is 20% to 40%, X, which indicates the ratio of the number of monomer residues of the anchor layer to the total number of monomer residues of the nanostructure AL is 60% to 85%, X represents the ratio of the number of monomer residues of the coating layer to the total number of monomer residues of the nanostructure. CL is between 1.5% and 4%, and 81.5% < (X CP +X AL +X CL 4. The plurality of spherical nanostructures according to any one of claims 1 to 3, wherein the ratio of the surface area of the spherical nanostructures to the surface area of the nanostructures is 100%.
5. The R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 R 17 , R 18 , R 19 , R 20 , R 21 , and R 22 The plurality of spherical nanostructures according to any one of claims 1 to 4, wherein at least 50% of all of the groups are covalently bonded.
6. The plurality of spherical nanostructures according to any one of claims 1 to 5, further comprising one or more radionuclides.
7. The radionuclide is 177 7. The plurality of spherical nanostructures of claim 6, wherein said nanostructure is Lu.
8. A plurality of spherical nanostructures according to any one of claims 1 to 7 for use as a medicament.
9. 8. A plurality of spherical nanostructures according to claim 6 or 7 for use in cancer treatment and / or imaging.
10. Use of a plurality of spherical nanostructures according to any one of claims 1 to 5 as carriers of radionuclides.
11. A pharmaceutical composition comprising a plurality of spherical nanostructures according to any one of claims 1 to 7, water, and at least one excipient.
12. 0.1-10 mg / ml thioglycerol, 0.03-3 mg / ml gentisic acid, and glycerol from 3 to 300 mg / ml; 12. The pharmaceutical composition of claim 11, further comprising:
13. 13. A pharmaceutical composition according to claim 11 or 12 for use as a medicament.
14. 13. A pharmaceutical composition according to claim 11 or 12, comprising a plurality of spherical nanostructures according to claim 6 or 7, for use in the treatment and / or imaging of cancer.
15. 1. A method for radiolabeling a plurality of spherical nanostructures with a multivalent cationic radionuclide, the method comprising: a) providing a solution having a pH of less than 3.5 and comprising a plurality of spherical nanostructures, preferably the nanostructures being as defined in any one of claims 1 to 5; b) contacting said solution of step a) with a pharma- ceutically acceptable salt of said radionuclide; and c) adjusting the pH of the solution to greater than 6; A method comprising:
16. In step a), the solution has a pH of less than 3, and / or step b) further comprises, after contacting the solution of step a) with a pharma- ceutically acceptable salt of the radionuclide, incubating the solution at a temperature between 40°C and 80°C for at least 15 minutes; and / or In step c), the pH is adjusted by mixing the solution of step b) with an aqueous buffer solution having a pH greater than 6. The method of claim 15.
17. An aqueous solution of the spherical nanostructures according to any one of claims 1 to 5, having a pH of less than 3.
5. an aqueous solution of a pharma- ceutically acceptable buffer having a pH of at least 6; and Instructions for use enabling the implementation of the radiolabeling method according to claim 15 or 16, Optionally, a mixing vessel, Optionally, equipment for sterile filtration, optionally, a pharma- ceutically acceptable diluent; Optionally, a centrifugal filter, and Optionally, devices for shielding against ionizing radiation; Kit including: